Compatibility of enzyme induced carbonate precipitation (EICP) and engineered biocrusts restoration (EBR) as strategies to curb fugitive dust formation from desert soils - Brian Scott; Edward Kavazanjian; Soumyadev Sarkar; Emmanuel Salifu; Ferran Garcia-Pichel (Ecological Engineering, 2026)

Biome-scale spatial patterns of avian abundance reveal proactive conservation opportunities in North American grasslands - Caleb P. Roberts; Victoria M. Donovan; Samantha M. Cady; Brandon P.M. Edwards; Scott Morford; David Naugle; Rheinhardt Scholtz; Dirac Twidwell; Daniel R. Uden; Dillon Fogarty (Biological Conservation, 2026)

Insights on the heterogeneity of thermal transfer in the chalk aquifer using fibre-optic distributed temperature sensing - Katerina Kyrkou; Joseph Kelly; Adam Booth; Fleur Loveridge; David Boon; Edward Hough; Lawrence Scott; Matthew Jackson; Adrian Butler; Daniel Perez; Athena Chalari (Geothermics, 2026)

Schwertmannite transformation under strongly-acidic conditions favoring jarosite precipitation: The effect of arsenic(V) and temperature - Neal Bailey; Niloofar Karimian; Scott G. Johnston; Mona Hosseinpour Moghaddam; Dane Lamb; Edward D. Burton (Journal of Hazardous Materials, 2026)

Retraction Note: Neurotoxic effects of the HCV core protein are mediated by sustained activation of ERK via TLR2 signaling - Amy D. Paulino; Kiren Ubhi; Edward Rockenstein; Anthony Adame; Leslie Crews; Scott Letendre; Ronald Ellis; Ian P. Everall; Igor Grant; Eliezer Masliah (Journal of NeuroVirology, 2026)

An integrated taxonomic approach reshapes the conservation status and distribution of the rare Mountain Needlefly, Leuctra monticola Hanson, 1941 (Plecoptera: Leuctridae) - Scott A. Grubbs; R. Edward DeWalt; Chris J. Verdone (Journal of Insect Conservation, 2026)
The morphological concept of the purportedly rare eastern Nearctic stonefly species Leuctra monticola Hanson, 1941 (Plecoptera: Leuctridae) is redefined following examination of type material and integrated morphological-molecular phylogenetic analyses using mitochondrial cytochrome c oxidase subunit 1 gene sequence data. These analyses included L. alexanderi Hanson, 1941, a species with an overlapping geographic distribution in the southern Appalachian Mountains, USA, and occasionally confused with L. monticola due to incomplete original descriptions and inconsistent line drawing styles. This paper was predicated on the inclusion of L. monticola in the previous (2015) and current (2025) Virginia Wildlife Action Plans as a Tier 2 (= Very High Conservation Need) species despite a lack of published locality data. Moreover, L. monticola was included as one of 33 Regional Species of Greatest Conservation Need (RSGCN) in the 13 state Northeast US Fish and Wildlife Service (USFWS) region from Virginia north to Maine and holds a NatureServe G1 (= Critically Imperiled) global ranking. Formal conservation assessments are currently being conducted on all 33 project species and funded by the regional states and the USFWS. Implications for insect conservation Our integrated morphological-molecular treatment that included L. alexanderi and L. monticola has led to the subsequent removal of the latter species from consideration as an RSGCN in the Northeast USFWS region. The distribution of L. monticola is narrowed to only foothill streams of the western flanks of the Great Smoky Mountains in east Tennessee, eliminated from the Virginia and North Carolina state lists, and aligns with the current NatureServe global ranking for this species. In contrast, L. alexanderi has a broad distribution in the Appalachian Mountains and adjacent Appalachian and Cumberland plateaus from northern Alabama east to northwestern South Carolina and north to southern New York. Digital light and scanning electron micrographs of diagnostic morphological characteristics of adult males and females of both species are provided, making correct determinations easier and geographic ranges more accurate. This paper has important ramifications for better decision making for potential conservation and management decisions, especially since L. monticola is now considered a species endemic to Tennessee and the Southeast USFWS region.

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Why controlling for habitat amount is critical for resolving the fragmentation debate - Lenore Fahrig; Carmen Galán‐Acedo; Brandon P. M. Edwards; Andrew K. Habrich; Amanda E. Martin; Cécile H. Albert; Victor Arroyo‐Rodríguez; Allison D. Binley; Jonathan R. Cole; Jessica K. Lockhart; Scott E. Nielsen; Federico Riva; et al. (Conservation Biology, 2026)

Lake sturgeon ( Acipenser fulvescens ) growth and longevity estimated from adult capture–mark–recapture data - Edward A. Baker; Scott F. Colborne; Nancy A. Auer; Kim T. Scribner; Douglas L. Larson; Andrew S. Briggs; Ronald M. Bruch; Margaret H. Stadig; Michael C. Donofrio (Journal of Fish Biology, 2026)
Effective fishery management policy depends on accurate life‐history data, particularly for harvested species. Longevity is a core life‐history trait that is directly related to annual survival and lifetime reproductive potential, but fish longevity is generally not well documented, particularly for long‐lived species. We used capture–mark–recapture data spanning 44 years as an alternative method to estimate sex‐specific adult lake sturgeon ( Acipenser fulvescens ) average annual growth and longevity for five populations in the Laurentian Great Lakes. We determined individual fish average annual growth and fit population and sex‐specific exponential lines for average annual growth as a function of fish length at initial capture. We used the exponential equations to estimate age for 180 cm fork length (FL) female and 160 cm FL male lake sturgeon from each population by sequential subtraction of annual growth increments and assuming age at onset of sexual maturity of 24 and 15 years for females and males, respectively. Average annual growth estimates varied between sexes and among populations and ranged from 0.26 to 1.15 cm year −1 . Estimated ages also varied among populations. Age estimated for a 160 cm FL male lake sturgeon across the five populations ranged from 90 to 279 years. Age for a 180 cm FL female across populations ranged from 99 to 427 years. Our data suggest lake sturgeons live much longer than currently believed. High longevity and inferentially higher adult survival have important implications for sturgeons in general and support conservative harvest regulations for lake sturgeon fisheries.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Pangenomes: new tools for ecological and evolutionary genomics - Bohao Fang; Scott V. Edwards (Trends in Ecology & Evolution, 2026)

Extracellular enzyme activities under adaptive multi-paddock and conventional grazing in grassland soils of western Canada - Dauren Kaliaskar; Edward W. Bork; Cameron N. Carlyle; Bharat M. Shrestha; Timm F. Döbert; Cole D. Gross; Upama Khatri-Chhetri; Mark S. Boyce; Scott X. Chang (Pedobiologia, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Goethite as an antimony host-phase: Atomic-scale retention mechanisms and the selectivity of commonly-applied extraction schemes - Mona Hosseinpour Moghaddam; Niloofar Karimian; Scott G. Johnston; Girish Choppala; Mohammad Rastegari; Edward D. Burton (Journal of Hazardous Materials, 2026)

Correction to: Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Correction: Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)

A decision support tool for rubble stabilization on coral reefs - Shu Kiu Leung; Tania M. Kenyon; Laurie J. Raymundo; Helen E. Fox; Nathan Cook; Kailash Cook; Alasdair J. Edwards; Eric E. Fisher; Arnaud J.T. Brival; Freda E. Nicholson; Robin W.L. Philippo; Andrew C.F. Taylor; et al. (Journal of Environmental Management, 2025)

Soil carbon stocks in cultivated Luvisols respond positively to long-term agronomic practices with different degrees of perennial forage inclusion - Jamin N. Achtymichuk; Miles F. Dyck; Sylvie A. Quideau; Erick R.S. Santos; Dick Puurveen; Scott R. Jeffrey; Edward W. Bork (Geoderma Regional, 2025)

Reconstruction of climatic and socio-economic impacts on the landscape of Northern Tuscany (Italy) over the last 2000 years based on palaeoecological and historical evidence - Scott Mensing; Theodore Dingemans; Edward Schoolman; Gianluca Piovesan; Adam Csank; Paolo Tomei; Simone Maria Collavini; Annamaria Pazienza; Federico Cantini; Jordan Palli; Giovani Zanchetta; Monica Bini (Anthropocene, 2025)

Congener Conflict: Invasive Barred Owl Landscape Use Across the Range of the Northern Spotted Owl - Julianna M. A. Jenkins; Natalie M. Rugg; Raymond J. Davis; Scott A. Gremel; Aaron Henderson; Edward Henson; Mark Higley; Holly D. Horan; Christopher McCafferty; Thomas Munger; David Press; Suzanne Reffler; et al. (Journal of Biogeography, 2025)
Aim To map the probability of landscape use of invading barred owls ( Strix varia ) across the range of the threatened northern spotted owl ( S. Occidentallis Caurina ) in the Pacific Northwest, USA , identifying environmental drivers of barred owl landscape use to inform targeted management interventions. Location Forests of the Pacific Northwest, USA. Taxon Barred Owl ( Strix varia ). Methods We deployed 4081 autonomous recording units ( ARUs ) within 1027 randomly selected long‐term monitoring sites consisting of 5‐km 2 hexagons in 2023. We processed audio recordings using convolutional neural networks to detect vocalisations. We applied single‐season occupancy models at both ARU station and hexagon scales to estimate barred owl landscape use and assess associations with environmental variables. Using top models, we mapped barred owl landscape use across the full US range of the northern spotted owl, an umbrella species for conservation of the pacific northwest old‐growth forest community. Results Barred owls were widely detected, with naïve occupancy at 86.8% at the 5‐km 2 hexagon scale. We observed regional variation, with the highest landscape use in the Oregon Coast region and lower landscape use in California regions and the Washington Eastern Cascades. Landscape use was positively associated with mature forest characteristics at both broad and fine scales and negatively associated with elevation and climatic water deficit. Cumulative detection probability exceeded 90% after 2 weeks at the hexagon scale and 4 weeks at the station scale, providing guidance for future barred owl monitoring efforts. Main Conclusions Our study reveals extensive, but not ubiquitous, barred owl distribution across the range of the northern spotted owl. The findings offer a decision‐support framework for prioritising targeted management actions, particularly in regions with lower rates of barred owl landscape use. The integration of passive acoustic monitoring and AI‐based detection demonstrates a scalable approach for invasive species monitoring and conservation planning to meet management objectives in dynamic forest landscapes.

Importance of near-bottom oceanographic data in modeling the distribution of eulachon bycatch in the U.S. West Coast shrimp trawl fishery - Leif K. Rasmuson; Scott D. Groth; Christopher A. Edwards; Eric S. Anderson; Matthew T.O. Blume; Kendall R. Smith (Frontiers in Marine Science, 2025)
Introduction Species distribution models (SDMs) are increasingly used in fisheries science to understand species’ spatial patterns and improve stock assessments. Method This study developed SDMs for eulachon smelt ( Thaleichthys pacificus ), a threatened, demersal forage fish often caught as bycatch in the United States West Coast ocean shrimp trawl fishery. Using ten years of observer data (2012–2021, n=19,749 with 25.4% being zeros), the study assessed the influence of static (e.g., substrate) and dynamic (e.g., ocean temperature, currents) environmental variables on eulachon abundance. Results The best-performing SDM included near-bottom temperature and current data, outperforming SDMs using only surface variables. Eulachon abundance peaked at ~150 m depth, especially over gravel substrates, and during nighttime. Although none of the SDM-based abundance indices significantly correlated with the Columbia River stock assessment index, bottom-based SDMs showed stronger alignment with the stock assessment (R=0.61, p=0.08 & R=0.62, p=0.07). Discussion Management implications are significant. Rock habitats were associated with higher eulachon bycatch, and vessels can use bottom-typing tools to avoid them. Also, delaying the season opener could reduce bycatch, as eulachon catch was reduced by 0.0109 mt per trawl over the interquartile range of day of the year. These findings can inform Best Management Practices (BMPs), which have historically led to regulatory changes such as the adoption of excluder grates and LED lights. Overall, incorporating near-bottom oceanographic data greatly enhanced predictive performance, especially for demersal species like eulachon. These mechanistic SDMs can be projected forward, aiding future management amid changing ocean conditions. While some discrepancies remain, this approach offers promising insights for adaptive fishery management and conservation of imperiled species like eulachon.

Late Quaternary environmental change in eastern Beringia - Alistair J. Monteath; Mary E. Edwards; Duane Froese; Lesleigh Anderson; Benjamin V. Gaglioti; Scott L. Cocker; Julie Brigham-Grette; Matthew J. Wooller; Bruce Finney; Mark B. Abbott (Quaternary Science Reviews, 2025)

Antimony(V) uptake by feroxyhyte (δ′-FeOOH): Insights from X-ray absorption spectroscopy and selective extractions - Mona Hosseinpour Moghaddam; Niloofar Karimian; Scott G. Johnston; Girish Choppala; Mohammad Rastegari; Edward D. Burton (Journal of Hazardous Materials, 2025)

Comparing Navcam dust devil detections to transient daytime convective vortex signatures in REMS pressure and ultraviolet data - Emily L. Mason; Scott D. Guzewich; Christopher Edwards; Álvaro Vicente-Retortillo; Daniel Viúdez-Moreiras (Icarus, 2025)

Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2025)
Barth syndrome (BTHS) is an X-linked recessive disorder characterized by cardiomyopathy, skeletal muscle myopathy and fatigue, growth restriction, and neutropenia. Neutropenia increases the risk of life-threatening bacterial infections, a major cause of death in individuals with BTHS. Currently, there is no curative treatment for BTHS or associated neutropenia. The development of therapeutic strategies to correct BTHS-associated neutropenia has been hindered by a limited understanding of the underlying molecular mechanisms involved. BTHS is caused by a mutation in the Tafazzin gene encoding a transacylase required for the maturation of cardiolipin, an inner mitochondrial membrane phospholipid crucial for mitochondrial structure and function. We introduced a BTHS patient’s point mutation ( TAZ D75H ) into the mouse Tafazzin enzyme’s critical acyltransferase site using CRISPR/Cas9 -mediated genome editing, resulting in a patient-tailored point mutant knock-in BTHS model ( Taz D75H ) that expresses a stable mutant Taz D75H protein lacking transacylase activity. Taz D75H mice were then used to investigate how loss of Tafazzin enzymatic activity impacts hematopoiesis. Male Taz D75H mice exhibited impaired granulopoiesis and neutropenia secondary to impaired function of hematopoietic progenitors. Furthermore, they demonstrated age-dependent neutrophil maturation impairment reflecting the variable neutropenia observed in BTHS patients. Additionally, male Taz D75H mice exhibit chronic lymphopenia that persists post Taz D75H bone marrow transplantation. Mechanistically, the TAZ D75H point mutation caused hematopoietic cell mitochondrial dysfunction in patient-derived immortalized TAZ D75H lymphoblasts, increasing reactive oxygen species production and mitochondrial membrane depolarization. Likewise, Cyclosporine A treatment rescued these mitochondrial phenotypes in vitro, confirming TAZ D75H mitochondrial dysfunction. Overall, our findings demonstrate that mitochondrial dysfunction secondary to TAFAZZIN loss of enzymatic function underlies BTHS-associated neutropenia and lymphopenia.

Sugarcane genotype by environment interaction (G × E) in clonal trials in the U.S. Texas Rio Grande Valley - James R. Todd; Orlando Coto Arbelo; Anna L. Hale; Yong-Bao Pan; Edwis O. Dufrene; David Verdun; Aliya Momotaz; Collins A. Kimbeng; Herman L. Waguespack; Andrew W. Scott; Edward Hernandez; Matthew Klostermann (Euphytica, 2025)

Context-dependent controls of periphyton across the littoral-benthic habitat of deep, clear lakes - Aldo San Pedro; Facundo Scordo; Carina Seitz; Edward M. Krynak; Scott F. Girdner; Joanna Blaszczak; Sudeep Chandra (Aquatic Sciences, 2025)

Soil microbial communities contribute to plant-soil feedback in an endangered legume - Rachel A. Brant; Rachel E. Becknell; Matthew A. Albrecht; Scott A. Mangan; Kelli Showalter; Burgund Bassüner; Christine E. Edwards (Plant and Soil, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Sex Differences in Head Acceleration Events in Law Enforcement Corrections Cadets - Carly R. Smith; Enora Le Flao; Samantha N. DeAngleo; Jeffrey J. Wing; Nathan A. Edwards; James A. Onate; Joshua A. Hagen; Scott Paur; Joshua Walters; Jaclyn B. Caccese (Annals of Biomedical Engineering, 2025)
Purpose Law enforcement cadets (LECs) undergo subject control technique training that may expose them to repetitive head impacts recorded as head acceleration events (HAEs) using instrumented mouthguards. Prior research suggests that sex and/or gender differences in HAE frequency and magnitude vary by sport. This study aimed to examine sex differences in HAE exposure among LECs during training. Methods We collected HAEs from 82 civilian LECs (16 females, mean age = 30 ± 9 years) using instrumented mouthguards. We compared peak linear acceleration (PLA) and peak rotational velocity (PRV) of HAEs > 5 g between sexes using a mixed-effects linear model, with sex and cohort as fixed-effect predictors and a random intercept for subject to account for repeated HAEs within individuals. Additionally, we assessed sex differences in the number of HAEs per athlete exposure using a negative binomial regression controlling for cohort. Results PLA was lower in female than male cadets (e.g., median PLA: females = 10.9 g, males = 12.3 g, p Conclusions Overall, sex differences in HAE frequency and magnitude during subject control technique trainings were minimal. When differences were observed, female cadets exhibited less frequent and less severe HAEs than male cadets. This finding suggests that current training practices, including sex- and/or skill-matched pairing, may effectively reduce HAE exposure risk to females.

Origins and Diversification of the Caatinga Dry Forest Endemic Avifauna - Hevana S. Lima; Gustavo A. Bravo; Diego Astúa; Daniele Mariz; Scott V. Edwards; Luciano N. Naka (Journal of Biogeography, 2025)
Aim Understanding the geographic origin of lineages is critical to comprehending their biogeographical and evolutionary histories and the historical connections among biomes. In northeastern Brazil, the Caatinga dry forest represents the largest and most biologically diverse patch of Seasonally Dry Tropical Forest in the Neotropics. Here, using the endemic avian taxa of the Caatinga, we aim to (i) infer their biogeographical origins and timing of diversification, (ii) investigate the relationships with taxa from other Neotropical domains and (iii) understand the processes driving the evolution and diversification of the Caatinga endemic avifauna. Location Neotropical Region. Taxon Birds. Methods We obtained previously published calibrated phylogenies of 40 bird species endemic to the Caatinga to reconstruct their ancestral geographic ranges through the R package BioGeoBEARS to infer and highlight the origins, mode and tempo of evolution of the Caatinga avian endemics. Results Our results suggest that most avian endemics (21 taxa) are related to lineages from open habitats, including other dry forests or savannas; less than a quarter of the species (9 taxa) likely colonised the Caatinga from adjacent humid forests; we also highlight in situ origins (6 taxa), and cladogenetic events playing an important role in the colonisation of the domain. Although most of the endemics seem to represent new arrivals from adjacent habitats, we also detected relatively old lineages that likely occupied these dry landscapes since the Miocene. A correlation between the age, origins of Caatinga birds and their degree of threat was also found. Main Conclusions We provide a much needed framework for the evolution and biogeographic diversification of the Caatinga Dry Forest. The spatio‐temporal patterns recovered here suggest an evolutionary history influenced not only by strict vicariance events but also by episodes of dispersal that likely played an important role in the origin of its avifauna. These events were likely influenced by major climatic and geological events that formed ancient corridors, allowing connections between the Caatinga and both dry and humid forests in South America.

Contrasting grazing practices alter plant community trajectories across western Canada’s grasslands with implications for ecosystem function - Timm F. Döbert; Lysandra A. Pyle; Carter Case; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang; Laio Silva Sobrinho; Majid Iravani; Mark S. Boyce (Agriculture, Ecosystems & Environment, 2025)

Burn parameters affect PAH emissions at conditions relevant for prescribed fires - Karl Töpperwien; Guillaume Vignat; Alexandra J. Feinberg; Conner Daube; Mitchell W. Alton; Edward C. Fortner; Manjula R. Canagaratna; Matthias F. Kling; Mary Johnson; Kari Nadeau; Scott Herndon; John T. Jayne; et al. (Atmospheric Pollution Research, 2025)

Transient Lymphatic Remodeling Follows Sub-Ablative High-Frequency Irreversible Electroporation Therapy in a 4T1 Murine Model - Savieay Esparza; Edward Jacobs; Jennifer H. Hammel; Sharon K. Michelhaugh; Nastaran Alinezhadbalalami; Margaret Nagai-Singer; Khan Mohammad Imran; Rafael V. Davalos; Irving C. Allen; Scott S. Verbridge; Jennifer M. Munson (Annals of Biomedical Engineering, 2025)
High-frequency irreversible electroporation (H-FIRE) is a minimally invasive local ablation therapy known to activate the adaptive immune system and reprogram the tumor microenvironment. Its predecessor, irreversible electroporation (IRE), transiently increases microvascular density and immune cell infiltration within the surviving non-ablated and non-necrotic tumor region, also known as the viable tumor region. However, the impact of pulse electric field therapies on lymphatic vessels, crucial for T-cell fate and maturation, remains unclear. This study investigates how sub-ablative H-FIRE (SA-HFIRE) affects lymphatic and blood microvascular remodeling in the 4T1 mammary mouse model. We conducted a temporal and spatial analysis to evaluate vascular changes in the viable tumor, peritumoral fat pad, and tumor-draining lymph node post-treatment. Histological examination showed a transient increase in blood vessel density on Day 1 post-treatment, followed by a spike in lymphatic vessel density in the viable tumor region on Day 3 post-treatment, increased lymphatic vessel density in the peripheral fat pad, and minimal remodeling of the tumor-draining lymph node within 3 days following treatment. Gene expression analysis indicated elevated levels of CCL21 and CXCL2 on Day 1 post-treatment, while VEGFA and VEGFC did not appear to contribute to vascular remodeling. Likewise, CCL21 protein content in tumor-draining axillary lymph nodes correlated with gene expression data from the viable tumor region. These findings suggest a dynamic shift in lymphatic and blood microvascular structures post-SA-HFIRE, potentially enhancing the adaptive immune response through CCL21-mediated lymphatic homing and subsequent lymph node microvascular remodeling. Future work will assess the immune and transport function of the microvasculature to inform experiments aimed at the application of adjuvant therapies during scenarios of tumor partial ablation.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Multi‐Species Telemetry Quantifies Current and Future Efficacy of a Remote Marine Protected Area - Morgan E. Gilmour; Kydd Pollock; Josh Adams; Barbara A. Block; Jennifer E. Caselle; Alex Filous; Alan M. Friedlander; Edward T. Game; Elliott L. Hazen; Marie Hill; Nick D. Holmes; Kevin D. Lafferty; et al. (Global Change Biology, 2025)
Large‐scale marine protected areas (LSMPAs; > 1000 km 2 ) provide important refuge for large mobile species, but most do not encompass species' ranges. To better understand current and future LSMPA value, we concurrently tracked nine species (seabirds, cetaceans, pelagic fishes, manta rays, reef sharks) at Palmyra Atoll and Kingman Reef (PKMPA) in the U.S. Pacific Islands Heritage Marine National Monument. PKMPA and the U.S. Exclusive Economic Zone encompassed 39% and 54% of species movements ( n = 83; tracking duration range: 0.5–350 days), respectively. Species distribution models indicated 73% of PKMPA contained highly suitable habitat. Under two projected future scenarios (SSP 1–2.6, “Sustainability”; SSP 3–7.0, “Rocky Road”), strong sea surface temperature gradients initially could cause abrupt oceanic change resulting in predicted habitat loss in 2040–2050, followed by an equilibrium response and regained habitat by 2090–2100. Current and future suitable habitats were available adjacent to PKMPA, suggesting that increased MPA size could enhance protection. Our three‐tiered approach combining animal tracking with publicly available remote sensing data and future projected environmental scenarios could be used to design, study, and monitor protected areas throughout the world. Holistic approaches that encompass diverse species and habitat use can enhance assessments of protected area designs. Animal telemetry and remote sensing may be helpful for ascertaining the extent to which other MPAs protect large mobile species in the future.

Experimental–numerical model comparison of a dynamic power cable for a floating offshore wind turbine - Anna Holcombe; Martyn Hann; Scott Brown; Shanshan Cheng; Robert Rawlinson-Smith; Rachel Nicholls-Lee; Tom Tosdevin; Emma Edwards; Kieran Monk (Ocean Engineering, 2025)

Quantifying impacts of seabird bycatch using genetic assignment: A case study of black-footed albatross in U.S. fisheries - Jessie N. Beck; Diana S. Baetscher; Claire Tobin; Scott V. Edwards; Simon Yung Wa Sin; Shannon Fitzgerald; Vanessa J. Tuttle; John Peschon; Wesley A. Larson (Biological Conservation, 2025)

Proteomic Analysis of Chronic Binge Alcohol-Induced Hippocampal and Anterior Cingulate Cortex Neuroadaptations in Simian Immunodeficiency Virus (SIV)-Infected Female Rhesus Macaques - Taylor Fitzpatrick-Schmidt; Amirsalar Mansouri; Jiri Adamec; Jennifer Klein; Larry Coleman; Kimberly N. Edwards; Liz Simon; Patricia E. Molina; Michael C. Salling; Scott Edwards (Journal of Neuroimmune Pharmacology, 2025)

A bioinformatic examination of indole-3-acetic acid biosynthesis in insecta and hexapoda - Joshua Natahusada; Scott W. Roy; Edward F. Connor (Arthropod-Plant Interactions, 2025)

Migration leads to nursery herd formation: evidence from a wild wood bison (Bison bison athabascae) population - Lee J. Hecker; Scott E. Nielsen; Mark A. Edwards (Mammal Research, 2025)

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Antimony-bearing schwertmannite transformation to goethite: A driver of antimony mobilization in acid mine drainage - Mohammad Rastegari; Niloofar Karimian; Scott G. Johnston; Girish Choppala; Mona Hosseinpour Moghaddam; Edward D. Burton (Journal of Hazardous Materials, 2024)

Antimony(V) sorption and coprecipitation with ferrihydrite: An examination of retention mechanisms and the selectivity of commonly-applied extraction procedures - Mona Hosseinpour Moghaddam; Niloofar Karimian; Scott G. Johnston; Girish Choppala; Mohammad Rastegari; Edward D. Burton (Journal of Hazardous Materials, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Antimony sorption to schwertmannite in acid sulfate environments - Mohammad Rastegari; Niloofar Karimian; Scott G. Johnston; Girish Choppala; Mona Hosseinpour Moghaddam; Edward D. Burton (Journal of Hazardous Materials, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Characterizing Head Acceleration Events in Law Enforcement Cadets During Subject Control Technique Training - Carly R. Smith; James A. Onate; Nathan A. Edwards; Joshua A. Hagen; Chris Kolba; Scott Paur; Joshua Walters; Jaclyn B. Caccese (Annals of Biomedical Engineering, 2024)
Law enforcement cadets (LECs) complete weeks of subject control technique training. Similar sport-related combat training has been shown to expose participants to head acceleration events (HAEs) that have potential to result in short- and long-term impairments. The purpose of this study was to describe the number and magnitude of HAEs in LECs throughout their training. 37 LECs (7 females; age = 30.6 ± 8.8 years; BMI = 30.0 ± 6.0) were recruited from a law enforcement organization. Participants wore instrumented mouthguards, which recorded all HAEs exceeding a resultant 5 g threshold for training sessions with the potential for HAEs. Participants completed three defensive tactics (DT) training sessions, a DT skill assessment (DTA), and three boxing sessions. Outcome measures included the number of HAEs, peak linear acceleration (PLA), and peak rotational velocity (PRV). There were 2758 true-positive HAEs recorded across the duration of the study. Boxing sessions accounted for 63.7% of all true-positive HAEs, while DT accounted for 31.4% and DTA accounted for 4.9%. Boxing sessions resulted in a higher number of HAEs per session ( F 2,28 = 48.588, p η p 2 = 0.776), and higher median PLA ( F 2,28 = 8.609, p = 0.001, η p 2 = 0.381) and median PRV ( F 2,28 = 11.297, p η p 2 = 0.447) than DT and DTA. The LECs experience a high number of HAEs, particularly during boxing sessions. Although this training is necessary for job duties, HAE monitoring may lead to modifications in training structure to improve participant safety and enhance recovery.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Floodplain morphology influences arsenic and antimony spatial distribution in a seasonal acid sulfate soil wetland - Gretchen Wichman; Scott G. Johnston; Edward D. Burton; Damien T. Maher (Journal of Hazardous Materials, 2024)

Manure and its biochar affect activities and stoichiometry of soil extracellular enzymes in croplands - Zhengfeng An; Cole D. Gross; Xinli Chen; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang (Journal of Soils and Sediments, 2024)

Estimating Biogeochemical Rates Using a Computationally Efficient Lagrangian Approach - Edward Gross; Rusty Holleman; Wim Kimmerer; Tamara Kraus; Brian Bergamaschi; Scott Burdick-Yahya; David Senn (Estuaries and Coasts, 2024)
Nutrient concentrations in many estuaries have increased over the past century due to increases in wastewater discharge and increased agricultural intensity, contributing to multiple environmental problems. Numerous biogeochemical and physical processes in estuaries influence nutrient concentrations during transport, resulting in complex spatial and temporal variability and challenges identifying predominant processes and their rates. Mechanistic models which require these rates to quantify biogeochemical processes become complex and difficult to calibrate as the number of processes and parameters grows, owing to the high dimensionality of the parameter space and the computational cost of simultaneously modeling the transport and transformations of constituents. We developed a modeling approach that decouples transport from transformations, enabling fast, data-driven exploration of the parameter space. The approach extracted information including water age, cumulative exposure to specific habitats, and mean water depth exposure from a hydrodynamic model. Using this information, a biogeochemical model was implemented to predict ammonium and nitrate concentrations in a Lagrangian frame. The model performed each simulation in milliseconds on a laptop computer, allowing the fitting of rate parameters for key transformations by optimization. The optimization used fixed station nitrate observations and the model was then validated against high-resolution mapping observations of ammonium and nitrate. The results suggest that the observed spatial and temporal variation can be largely represented with five transformation processes and their associated rates. Dissolved inorganic nitrogen (DIN) losses occurred only in shallow vegetated areas in the model, highlighting that biogeochemical processes in these areas should be included in DIN models.

Adaptive multi-paddock grazing increases mineral associated soil carbon in Northern grasslands - Upama Khatri-Chhetri; Karen A. Thompson; Sylvie A. Quideau; Mark S. Boyce; Scott X. Chang; Edward W. Bork; Cameron N. Carlyle (Agriculture, Ecosystems & Environment, 2024)

Extreme iron cycling in a coastal lake-lagoon system driven by interactions between climate and entrance management - Scott G. Johnston; Thor Aaso; Damien T. Maher; Edward D. Burton; Mitchell Call; Mathew Birch; John Schmidt; Angus Ferguson (Science of The Total Environment, 2024)

Persistence and evidence for accelerated biodegradation of streptomycin in agricultural soils - Megan Demars; Tim McDowell; Justin B. Renaud; Andrew Scott; Michael Fruci; Edward Topp (Science of The Total Environment, 2024)

SO2 emission rates and incorporation into the air pollution dispersion forecast during the 2021 eruption of Fagradalsfjall, Iceland - Melissa A. Pfeffer; Santiago Arellano; Sara Barsotti; Guðrún Nína Petersen; Talfan Barnie; Evgenia Ilyinskaya; Tryggvi Hjörvar; Enikö Bali; Gro B.M. Pedersen; Gunnar B. Guðmundsson; Kristín Vogfjorð; Eemu Johannes Ranta; et al. (Journal of Volcanology and Geothermal Research, 2024)

CAUSES AND INCIDENCE OF FAILURE TO LITTER IN CONTROL ratS FROM EXTENDED ONE-GENERATION REPRODUCTIVE TOXICITY STUDIES - O. Greville-Heygate; P. Edwards; S. Renaut; P. Scott; M. Levi (Journal of Comparative Pathology, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

Mineral dust optical properties for remote sensing and global modeling: A review - Patricia Castellanos; Peter Colarco; W. Reed Espinosa; Scott D. Guzewich; Robert C. Levy; Ron L. Miller; Mian Chin; Ralph A. Kahn; Osku Kemppinen; Hans Moosmüller; Edward P. Nowottnick; Adriana Rocha-Lima; et al. (Remote Sensing of Environment, 2024)

Cytokinin biosynthesis in Hexapoda and Insecta: a bioinformatic analysis - Nate Mooi; Scott W. Roy; Edward F. Connor (Arthropod-Plant Interactions, 2024)

Episodic population fragmentation and gene flow reveal a trade‐off between heterozygosity and allelic richness - Peta Hill; Chris R. Dickman; Russell Dinnage; Richard P. Duncan; Scott V. Edwards; Aaron Greenville; Stephen D. Sarre; Emily J. Stringer; Glenda M. Wardle; Bernd Gruber (Molecular Ecology, 2023)
In episodic environments like deserts, populations of some animal species exhibit irregular fluctuations such that populations are alternately large and connected or small and isolated. Such dynamics are typically driven by periodic resource pulses due, for example, to large but infrequent rainfall events. The repeated population bottlenecks resulting from fragmentation should lower genetic diversity over time, yet species undergoing these fluctuations appear to maintain high levels of genetic diversity. To resolve this apparent paradox, we simulated a metapopulation of constant size undergoing repeat episodes of fragmentation and change in gene flow to mimic outcomes experienced by mammals in an Australian desert. We show that episodic fragmentation and gene flow have contrasting effects on two measures of genetic diversity: heterozygosity and allelic richness. Specifically, fragmentation into many, small subpopulations, coupled with periods of infrequent gene flow, preserves allelic richness at the expense of heterozygosity. In contrast, fragmentation into a few, large subpopulations maintains heterozygosity at the expense of allelic richness. The strength of the trade‐off between heterozygosity and allelic richness depends on the amount of gene flow and the frequency of gene flow events. Our results imply that the type of genetic diversity maintained among species living in strongly fluctuating environments will depend on the way populations fragment, with our results highlighting different mechanisms for maintaining allelic richness and heterozygosity in small, fragmented populations.

Light to moderate long-term grazing enhances ecosystem carbon across a broad climatic gradient in northern temperate grasslands - Edward W. Bork; Daniel B. Hewins; Eric G. Lamb; Cameron N. Carlyle; Mark P. Lyseng; Scott X. Chang; Michael J. Alexander; Walter D. Willms; Majid Iravani (Science of The Total Environment, 2023)

Decadal impacts of wildfire fuel reduction treatments on ecosystem characteristics and fire behavior in alaskan boreal forests - Melissa A. Boyd; Xanthe J. Walker; Jennifer Barnes; Gerardo Celis; Scott J. Goetz; Jill F. Johnstone; Nicholas T. Link; April M. Melvin; Lisa Saperstein; Edward A.G. Schuur; Michelle C. Mack (Forest Ecology and Management, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Differential sensitivity of above- and belowground plant biomass to drought and defoliation in temperate grasslands - Amgaa Batbaatar; Cameron N. Carlyle; Edward W. Bork; Scott X. Chang; James F. Cahill (Agriculture, Ecosystems & Environment, 2023)

Mechanisms and models for industry engagement in collaborative research in commercial fisheries - Matthew R. Baker; Robert Alverson; Ruth Christiansen; Keith Criddle; Danny Eilertsen; Robert J. Foy; John Gauvin; Scott E. Goodman; Leigh Habegger; Bradley P. Harris; Nicole Kimball; Anna Malek Mercer; et al. (Frontiers in Marine Science, 2023)
Data and insights from fishers are essential sources of information to advance understanding of fishery and ecosystem dynamics. Incorporating fisher and industry knowledge holds prospects for improving marine science and fisheries management. We address cooperative research in the context of collaboration between fishers, scientists, industries, universities, and agencies to develop applied research to understand marine ecosystems, inform fishery management, enhance sustainability, govern resource use, and investigate social-economic dynamics. We leverage the insights of more than 100 research scientists, fisheries managers, industry representatives, and fishers to outline actionable recommendations for effective approaches and mechanisms to integrate industry data, perspectives, and insights in fisheries science. We also highlight opportunities and address challenges and limitations to such collaboration.

Incorporating caudate species susceptibilities and climate change into models of Batrachochytrium salamandrivorans risk in the United States of America - Matthew Grisnik; Matthew J. Gray; Jonah Piovia-Scott; Edward Davis Carter; William B. Sutton (Biological Conservation, 2023)

Complement component C1q is an immunological rheostat that regulates Fc:Fc$$γ$$R interactions - Edward C. So; Hua Zhou; Ariana Greenwell; Erin E. Burch; Yaping Ji; Emmanuel Y. Mérigeon; Henrik S. Olsen; Søren M. Bentzen; David S. Block; Xiaoyu Zhang; Scott E. Strome (Immunogenetics, 2023)

Wildfire Smoke Monitoring for Agricultural Safety and Health in Rural Washington - Claire Schollaert; Elena Austin; Edmund Seto; June Spector; Scott Waller; Edward Kasner (Journal of Agromedicine, 2023)

Examining the performance of alternative harvest regulations for short-lived taxa: A case study of Florida Bay scallop management - Lisa Chong; Nicholas Fisch; John Scott Borsum; Jennifer Granneman; Diana Perry; Gabrielle Love; Brittany Hall-Scharf; Robert Botta; Kai Lorenzen; Edward Camp; Zachary Siders (Fisheries Research, 2023)

Greener residential environment is associated with increased bacterial diversity in outdoor ambient air - Jennifer N. Styles; Andrey I. Egorov; Shannon M. Griffin; Jo Klein; J.W. Scott; Elizabeth A. Sams; Edward Hudgens; Chris Mugford; Jill R. Stewart; Kun Lu; Ilona Jaspers; Scott P. Keely; et al. (Science of The Total Environment, 2023)

Behavioral habitat selection of wood bison (Bison bison athabascae) in boreal forests - Lee J. Hecker; Mark A. Edwards; Scott E. Nielsen (Mammal Research, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Targeting Redundant ROBO1 and SDF-1 Pathways Prevents Adult Hemangioblast Derived-EPC and CEC Activity Effectively Blocking Tumor Neovascularization - Anitha K. Shenoy; Liya Pi; Alexander P. Ligocki; Koji Hosaka; Christopher R. Cogle; Edward W. Scott (Stem Cell Reviews and Reports, 2023)

Martian nonmigrating atmospheric tides in the thermosphere and ionosphere at solar minimum - Scott A. Thaller; Laila Andersson; Edward Thiemann; Marcin D. Pilinski; Xiaohua Fang; Meredith Elrod; Paul Withers; Stephen Bougher; Geoffrey Jenkins (Icarus, 2023)

Whole‐genome phylogeography of the blue‐faced honeyeater ( Entomyzon cyanotis ) and discovery and characterization of a neo‐Z chromosome - John T. Burley; Sophia C. M. Orzechowski; Simon Yung Wa Sin; Scott V. Edwards (Molecular Ecology, 2023)
Whole‐genome surveys of genetic diversity and geographic variation often yield unexpected discoveries of novel structural variation, which long‐read DNA sequencing can help clarify. Here, we report on whole‐genome phylogeography of a bird exhibiting classic vicariant geographies across Australia and New Guinea, the blue‐faced honeyeater ( Entomyzon cyanotis ), and the discovery and characterization of a novel neo‐Z chromosome by long‐read sequencing. Using short‐read genome‐wide SNPs, we inferred population divergence events within E. cyanotis across the Carpentarian and other biogeographic barriers during the Pleistocene (~0.3–1.7 Ma). Evidence for introgression between nonsister populations supports a hypothesis of reticulate evolution around a triad of dynamic barriers around Pleistocene Lake Carpentaria between Australia and New Guinea. During this phylogeographic survey, we discovered a large (134 Mbp) neo‐Z chromosome and we explored its diversity, divergence and introgression landscape. We show that, as in some sylvioid passerine birds, a fusion occurred between chromosome 5 and the Z chromosome to form a neo‐Z chromosome; and in E. cyanotis , the ancestral pseudoautosomal region (PAR) appears nonrecombinant between Z and W, along with most of the fused chromosome 5. The added recombination‐suppressed portion of the neo‐Z (~37.2 Mbp) displays reduced diversity and faster population genetic differentiation compared with the ancestral‐Z. Yet, the new PAR (~17.4 Mbp) shows elevated diversity and reduced differentiation compared to autosomes, potentially resulting from introgression. In our case, long‐read sequencing helped clarify the genomic landscape of population divergence on autosomes and sex chromosomes in a species where prior knowledge of genome structure was still incomplete.

Simulating the Impacts of an Applied Dynamic Adaptive Pathways Plan Using an Agent-Based Model: A Tauranga City, New Zealand, Case Study - Andrew Allison; Scott Stephens; Paula Blackett; Judy Lawrence; Mark Edward Dickson; Yvonne Matthews (Journal of Marine Science and Engineering, 2023)
Climate change and relative sea-level rise (RSLR) will increasingly expose coastal cities to coastal flooding, erosion, pluvial and fluvial flooding, episodic storm-tide flooding and eventually, permanent inundation. Tools are needed to support adaptive management approaches that allow society to adapt incrementally by making decisions now without creating path dependency and compromising decision-making options in the future. We developed an agent-based model that integrates climate-related physical hazard drivers and socio-economic drivers. We used it to explore how adaptive actions might be sequentially triggered within a low-elevation coastal city in New Zealand, in response to various climate change and socio-economic scenarios. We found that different adaptive actions are triggered at about the same RSLR level regardless of shared socio-economic pathway/representative concentration pathway scenario. The timing of actions within each pathway is dictated mainly by the rate of RSLR and the timing and severity of storm events. For the representative study site, the model suggests that the limits for soft and hard protection will occur around 30 cm RSLR, fully-pumped water systems are viable to around 35 cm RSLR and infrastructure upgrades and policy mechanisms are feasible until between 40 cm and 75 cm RSLR. After 75 cm RSLR, active retreat is the only remaining adaptation pathway.

Corrigendum to “What’s the catch? Examining optimal longline fishing gear configurations to minimize negative impacts on non-target species” [Mar. Policy 143 (2022) 105186] - Molly Scott; Edward Cardona; Kaylee Scidmore-Rossing; Mark Royer; Jennifer Stahl; Melanie Hutchinson (Marine Policy, 2023)

Bioaccessibility of iron in pearl millet flour contaminated with different soil types - Molly Muleya; Scott D. Young; Martin R. Broadley; Edward J.M. Joy; Prosper Chopera; Elizabeth H. Bailey (Food Chemistry, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Agroforestry perennials reduce nitrous oxide emissions and their live and dead trees increase ecosystem carbon storage - Cole D. Gross; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang (Global Change Biology, 2022)
Agroforestry systems (AFS) contribute to carbon (C) sequestration and reduction in greenhouse gas emissions from agricultural lands. However, previously understudied differences among AFS may underestimate their climate change mitigation potential. In this 3‐year field study, we assessed various C stocks and greenhouse gas emissions across two common AFS (hedgerows and shelterbelts) and their component land uses: perennial vegetated areas with and without trees (woodland and grassland, respectively), newly planted saplings in grassland, and adjacent annual cropland in central Alberta, Canada. Between 2018 and 2020 (~April–October), nitrous oxide emissions were 89% lower under perennial vegetation relative to the cropland (0.02 and 0.18 g N m −2 year −1 , respectively). In 2020, heterotrophic respiration in the woodland was 53% lower in shelterbelts relative to hedgerows (279 and 600 g C m −2 year −1 , respectively). Within the woodland, deadwood C stock was particularly important in hedgerows (35 Mg C ha −1 or 7% of ecosystem C) relative to shelterbelts (2 Mg C ha −1 or −1 found in the cropland, grassland, planted saplings treatment, and woodland, respectively. Shelterbelt and hedgerow woodlands contained 2.09 and 3.03 times more C, respectively, than adjacent cropland. Our findings emphasize the importance of AFS for fostering C sequestration and reducing greenhouse gas emissions and, in particular, retaining hedgerows (legacy woodland) and their associated deadwood across temperate agroecosystems will help mitigate climate change.

Simulated heat wave events increase CO2 and N2O emissions from cropland and forest soils in an incubation experiment - Zhengfeng An; Edward W. Bork; David Olefeldt; Cameron N. Carlyle; Scott X. Chang (Biology and Fertility of Soils, 2022)

Grazing by an endemic atyid shrimp controls microbial communities in the Hawaiian anchialine ecosystem - Justin C. Havird; Pamela M. Brannock; Reyn M. Yoshioka; Rebecca C. Vaught; Kaile'a Carlson; Collin Edwards; Allison Tracy; Cornelia W. Twining; Yun Zheng; David Chai; Alan E. Wilson; Nelson G. Hairston; et al. (Limnology and Oceanography, 2022)
Animals often shape environmental microbial communities, which can in turn influence animal gut microbiomes. Invasive species in critical habitats may reduce grazing pressure from native species and shift microbial communities. The landlocked coastal ponds, pools, and caves that make up the Hawaiian anchialine ecosystem support an endemic shrimp ( Halocaridina rubra ) that grazes on diverse benthic microbial communities, including orange cyanobacterial‐bacterial crusts and green algal mats. Here, we asked how shrimp: (1) shape the abundance and composition of microbial communities, (2) respond to invasive fishes, and (3) whether their gut microbiomes are affected by environmental microbial communities. We demonstrate that ecologically relevant levels of shrimp grazing significantly reduce epilithon biomass. Shrimp grazed readily and grew well on both orange crusts and green mat communities. However, individuals from orange crusts were larger, despite crusts having reduced concentrations of key fatty acids. DNA profiling revealed shrimp harbor a resident gut microbiome distinct from the environment, which is relatively simple and stable across space (including habitats with different microbial communities) and time (between wild‐caught individuals and those maintained in the laboratory for >2 yr). DNA profiling also suggests shrimp grazing alters environmental microbial community composition, possibly through selective consumption and/or physical interactions. While this work suggests grazing by endemic shrimp plays a key role in shaping microbial communities in the Hawaiian anchialine ecosystem, the hypothesized drastic ecological shifts resulting from invasive fishes may be an oversimplification as shrimp may largely avoid predation. Moreover, environmental microbial communities may have little influence on shrimp gut microbiomes.

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Human health implications from consuming eggs produced near a derelict metalliferous mine: a case study - Andrea Sartorius; Matthew Johnson; Scott Young; Malcolm Bennett; Kerstin Baiker; Paul Edwards; Lisa Yon (Food Additives & Contaminants: Part A, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Uncrewed Ocean Gliders and Saildrones Support Hurricane Forecasting and Research - Travis Miles; Dongxiao Zhang; Gregory Foltz; Jun Zhang; Christian Meinig; Francis Bringas; Joaquin Triñanes; Matthieu Le Hénaff; Maria Aristizabal Vargas; Sam Coakley; Catherine Edwards; Donglai Gong; et al. (Oceanography, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Animal‐borne video from a sea turtle reveals novel anti‐predator behaviors - Jenna L. Hounslow; Oliver J. D. Jewell; Sabrina Fossette; Scott Whiting; Anton D. Tucker; Anthony Richardson; David Edwards; Adrian C. Gleiss (Ecology, 2021)

Macroalgal defense phenotype correlates with herbivore abundance - Scott S. Gabara; Benjamin P. Weitzman; Brenda H. Konar; Matthew S. Edwards (Marine Biology, 2020)

Evidence for the Pleistocene Arc Hypothesis from genome‐wide SNPs in a Neotropical dry forest specialist, the Rufous‐fronted Thornbird (Furnariidae: Phacellodomus rufifrons ) - Eamon C. Corbett; Gustavo A. Bravo; Fabio Schunck; Luciano N. Naka; Luís F. Silveira; Scott V. Edwards (Molecular Ecology, 2020)
South American dry forests have a complex and poorly understood biogeographic history. Based on the fragmented distribution of many Neotropical dry forest species, it has been suggested that this biome was more widely distributed and contiguous under drier climate conditions in the Pleistocene. To test this scenario, known as the Pleistocene Arc Hypothesis, we studied the phylogeography of the Rufous‐fronted Thornbird ( Phacellodomus rufifrons ), a widespread dry forest bird with a disjunct distribution closely matching that of the biome itself. We sequenced mtDNA and used ddRADseq to sample 7,167 genome‐wide single‐nucleotide polymorphisms from 74 P. rufifrons individuals across its range. We found low genetic differentiation over two prominent geographic breaks — particularly across a 1,000 km gap between populations in Bolivia and Northern Peru. Using demographic analyses of the joint site frequency spectrum, we found evidence of recent divergence without subsequent gene flow across those breaks. By contrast, parapatric morphologically distinct populations in northeastern Brazil show high genetic divergence with evidence of recent gene flow. These results, in combination with our paleoclimate species distribution modelling, support the idea that currently disjunct patches of dry forest were more connected in the recent past, probably during the Middle and Late Pleistocene. This notion fits the major predictions of the Pleistocene Arc Hypothesis and illustrates the importance of comprehensive genomic and geographic sampling for examining biogeographic and evolutionary questions in complex ecosystems like Neotropical dry forests.

Cross‐species transmission and evolutionary dynamics of canine distemper virus during a spillover in African lions of Serengeti National Park - Julie K. Weckworth; Brian W. Davis; Edward Dubovi; Nicholas Fountain‐Jones; Craig Packer; Sarah Cleaveland; Meggan E. Craft; Ernest Eblate; Michael Schwartz; L. Scott Mills; Melody Roelke‐Parker (Molecular Ecology, 2020)
The outcome of pathogen spillover from a reservoir to a novel host population can range from a “dead‐end” when there is no onward transmission in the recipient population, to epidemic spread and even establishment in new hosts. Understanding the evolutionary epidemiology of spillover events leading to discrete outcomes in novel hosts is key to predicting risk and can lead to a better understanding of the mechanisms of emergence. Here we use a Bayesian phylodynamic approach to examine cross‐species transmission and evolutionary dynamics during a canine distemper virus (CDV) spillover event causing clinical disease and population decline in an African lion population ( Panthera leo ) in the Serengeti Ecological Region between 1993 and 1994. Using 21 near‐complete viral genomes from four species we found that this large‐scale outbreak was likely ignited by a single cross‐species spillover event from a canid reservoir to noncanid hosts Crocuta crocuta ) could have acted as the proximate source of CDV exposure in lions. We report 13 nucleotide substitutions segregating CDV strains found in canids and noncanids. Our results are consistent with the hypothesis that virus evolution played a role in CDV emergence in noncanid hosts following spillover during the outbreak, suggest that host barriers to clinical infection can limit outcomes of CDV spillover in novel host species.

Deforestation leakage undermines conservation value of tropical and subtropical forest protected areas - Scott Alan Ford; Martin Rudbeck Jepsen; Naomi Kingston; Edward Lewis; Thomas M. Brooks; Brian MacSharry; Ole Mertz (Global Ecology and Biogeography, 2020)
Aim The establishment of protected areas is among the most widespread responses to mitigate species loss. Although protected areas are often assumed to have conservation benefits, negative impacts have also been documented. One potential negative outcome is leakage, whereby protected areas displace land‐use activities harmful to conservation into adjacent areas. This can undermine protection by accelerating loss of species or skewing judgements of effectiveness. This study assessed the prevalence of deforestation leakage in a pan‐tropical and subtropical selection of 120 protected areas. Location Tropical and subtropical forest regions of America, Africa and Asia. Time period 2001–2017. Major taxa studied Threatened species of amphibians, birds and terrestrial mammals. Methods We used Global Forest Change data to assess the average yearly rate of deforestation in protected areas, protected area buffer zones and statistically matched, unprotected control areas. We calculated and compared irreplaceability of habitat for threatened amphibian, bird and terrestrial mammal species between protected areas and buffer zones. Results In 55 cases, deforestation rates were higher in buffer zones than in protected and control areas, suggesting a relatively high prevalence of deforestation leakage stemming from protected areas. In 78.2% of documented leakage cases, reduced deforestation in protected areas was not sufficient to offset the amount of deforestation in 10 km buffer zones to a level that would be expected without protection. In 90.9% of leakage cases, the irreplaceability of species in the 10 km buffer zone was greater than that of the protected area, implying a negative impact of leakage on threatened species. Main conclusions The results suggest that protected areas are generally effective at preventing deforestation within their jurisdiction; however, leakage patterns can undermine conservation success because buffer zones often contain habitat for threatened species. We recommend accounting for the possibility of leakage when designing new protected areas and networks.

Geographic variation in responses of kelp forest communities of the California Current to recent climatic changes - Rodrigo Beas‐Luna; Fiorenza Micheli; C. Brock Woodson; Mark Carr; Dan Malone; Jorge Torre; Charles Boch; Jennifer E. Caselle; Matt Edwards; Jan Freiwald; Scott L. Hamilton; Arturo Hernandez; et al. (Global Change Biology, 2020)
The changing global climate is having profound effects on coastal marine ecosystems around the world. Structure, functioning, and resilience, however, can vary geographically, depending on species composition, local oceanographic forcing, and other pressures from human activities and use. Understanding ecological responses to environmental change and predicting changes in the structure and functioning of whole ecosystems require large‐scale, long‐term studies, yet most studies trade spatial extent for temporal duration. We address this shortfall by integrating multiple long‐term kelp forest monitoring datasets to evaluate biogeographic patterns and rates of change of key functional groups (FG) along the west coast of North America. Analysis of data from 469 sites spanning Alaska, USA, to Baja California, Mexico, and 373 species (assigned to 18 FG) reveals regional variation in responses to both long‐term (2006–2016) change and a recent marine heatwave (2014–2016) associated with two atmospheric and oceanographic anomalies, the “Blob” and extreme El Niño Southern Oscillation (ENSO). Canopy‐forming kelps appeared most sensitive to warming throughout their range. Other FGs varied in their responses among trophic levels, ecoregions, and in their sensitivity to heatwaves. Changes in community structure were most evident within the southern and northern California ecoregions, while communities in the center of the range were more resilient. We report a poleward shift in abundance of some key FGs. These results reveal major, ongoing region‐wide changes in productive coastal marine ecosystems in response to large‐scale climate variability, and the potential loss of foundation species. In particular, our results suggest that coastal communities that are dependent on kelp forests will be more impacted in the southern portion of the California Current region, highlighting the urgency of implementing adaptive strategies to sustain livelihoods and ensure food security. The results also highlight the value of multiregional integration and coordination of monitoring programs for improving our understanding of marine ecosystems, with the goal of informing policy and resource management in the future.

Carbon accumulation in agroforestry systems is affected by tree species diversity, age and regional climate: A global meta‐analysis - Zilong Ma; Han Y. H. Chen; Edward W. Bork; Cameron N. Carlyle; Scott X. Chang (Global Ecology and Biogeography, 2020)
Aim Agroforestry is a globally practised system of land use for achieving greater and more diverse biomass production, but it has other ecological benefits, such as mitigation of climate change. Despite this, long‐term carbon (C) accumulation in different components of agroforestry systems, the drivers for C accumulation and the linkages between tree biomass and soil C stocks remain unclear. Location Global. Time period From 1989 to 2019. Major taxa studied Trees. Methods Here, we report on a global meta‐analysis based on 141 studies to identify patterns of C accumulation in tree‐based agroforestry systems compared with sole cropland and pasture. Results We found that agroforestry systems had, on average, 46.1 Mg/ha (95% confidence interval, 36.4–55.8 Mg/ha) more C in tree biomass compared with sole cropland‐ or pasture‐based land uses without trees. Furthermore, agroforestry systems with multiple tree species contained greater biomass C stocks and accumulated biomass C faster than systems with a single tree species. The effect of agroforestry practices on soil C stock increased with tree age, although such increases varied among climatic zones. Agroforestry systems in tropical zones had the ability to increase soil C to peak levels quickly, whereas soil C in temperate zones increased at a slower rate but peaked at a greater overall soil C level. Our structural equation model did not detect a direct linkage between biomass C and changes in total soil C stock in agroforestry systems. Main conclusions Our results demonstrate that planting multiple tree species in agroforestry systems is an important strategy to increase biomass C sequestration, with regional climate affecting the temporal change of soil C in response to agroforestry practices.

Old growth Afrotropical forests critical for maintaining forest carbon - John R. Poulsen; Vincent P. Medjibe; Lee J. T. White; Zewei Miao; Ludovic Banak‐Ngok; Chris Beirne; Connie J. Clark; Aida Cuni‐Sanchez; Mathias Disney; Jean‐Louis Doucet; Michelle E. Lee; Simon L. Lewis; et al. (Global Ecology and Biogeography, 2020)
Aim Large trees [≥ 70 cm diameter at breast height (DBH)] contribute disproportionately to aboveground carbon stock (AGC) across the tropics but may be vulnerable to changing climate and human activities. Here we determine the distribution, drivers and threats to large trees and high carbon forest. Location Central Africa. Time period Current. Major taxa studied Trees. Methods Using Gabon's new National Resource Inventory of 104 field sites, AGC was calculated from 67,466 trees from 578 species and 97 genera. Power and Michaelis–Menten models assessed the contribution of large trees to AGC. Environmental and anthropogenic drivers of AGC, large trees, and stand variables were modelled using Akaike’s information criterion (AIC) weights to calculate average regression coefficients for all p ossible models. Results Mean AGC for trees ≥ 10 cm DBH in Gabonese forestlands was 141.7 Mg C/ha, with averages of 166.6, 171.3 and 96.6 Mg C/ha in old growth, concession and secondary forest. High carbon forests occurred where large trees are most abundant: 31% of AGC was stored in large trees (2.3% of all stems). Human activities largely drove variation in AGC and large trees, but climate and edaphic conditions also determined stand variables (basal area, tree height, wood density, stem density). AGC and large trees increased with distance from human settlements; AGC was 40% lower in secondary than primary and concession forests and 33% higher in protected than non‐managed areas. Main conclusions AGC and large trees were negatively associated with human activities, highlighting the importance of forest management. Redefining large trees as ≥ 50 cm DBH (4.3% more stems) would account for 20% more AGC. This study demonstrates that protecting relatively undisturbed forests can be disproportionately effective in conserving carbon and suggests that including sustainable forestry in programs like reduced emissions for deforestation and forest degradation could maintain carbon dense forests in logging concessions that are a large proportion of remaining Central African forests.

Loss of vacuolar acidity results in iron-sulfur cluster defects and divergent homeostatic responses during aging in Saccharomyces cerevisiae - Kenneth L. Chen; Toby N. Ven; Matthew M. Crane; Matthew L. C. Brunner; Adrian K. Pun; Kathleen L. Helget; Katherine Brower; Dexter E. Chen; Ha Doan; Justin D. Dillard-Telm; Ellen Huynh; Yen-Chi Feng; et al. (GeroScience, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Postglacial vegetation community change over an elevational gradient on the western Kenai Peninsula, Alaska: pollen records from Sunken Island and Choquette Lakes - R. Scott Anderson; Edward Berg; Chris Williams; Tami Clark (Journal of Quaternary Science, 2019)
The Kenai Peninsula of south‐central Alaska is a region of high topographic diversity with a complex glacial history. The sedimentary record of two small lakes [Sunken Island (SIL; 76 m a.s.l.) in the Kenai Lowlands; Choquette (CL; 527 m a.s.l.) in the Caribou Hills upland] exemplifies the postglacial development of the conifer–hardwood forest over an elevational range there. A herb–shrub tundra was established at both sites after deglaciation. By ~10.7 ka, poplar ( Populus sp.) and alder ( Alnus ) dominated the lowland forest, while alder with minor poplar occurred at the upland site. Lake levels lower than today occurred during the early Holocene until ~8 ka. Subsequently at SIL, the near‐modern Kenai birch ( Betula kenaica ) – white spruce ( Picea glauca ) forest maintained prominence throughout the Holocene. However, at CL, alder dominated with dwarf birch and other subshrubs; small amounts of white spruce arrived ~5.2 ka. Black spruce ( Picea mariana ) grew around SIL by ~4 ka, but never gained prominence at CL. Fire, a prominent agent of disturbance in the Kenai Lowlands since ~8 ka, was essentially absent at the hardwood‐dominated upland site before ~6 ka, and rare thereafter. This suggests an important link between fire and spruce in Kenai forests.

Long-Term Grazing Accelerated Litter Decomposition in Northern Temperate Grasslands - Xiaozhu Chuan; Cameron N. Carlyle; Edward W. Bork; Scott X. Chang; Daniel B. Hewins (Ecosystems, 2018)

Cereal cultivation as a correlate of high social status in medieval Iceland - Scott Riddell; Egill Erlendsson; Guðrún Gísladóttir; Kevin J. Edwards; Jesse Byock; Davide Zori (Vegetation History and Archaeobotany, 2018)

Cross‐scale controls on carbon emissions from boreal forest megafires - Xanthe J. Walker; Brendan M. Rogers; Jennifer L. Baltzer; Steven G. Cumming; Nicola J. Day; Scott J. Goetz; Jill F. Johnstone; Edward A. G. Schuur; Merritt R. Turetsky; Michelle C. Mack (Global Change Biology, 2018)
Climate warming and drying is associated with increased wildfire disturbance and the emergence of megafires in North American boreal forests. Changes to the fire regime are expected to strongly increase combustion emissions of carbon (C) which could alter regional C balance and positively feedback to climate warming. In order to accurately estimate C emissions and thereby better predict future climate feedbacks, there is a need to understand the major sources of heterogeneity that impact C emissions at different scales. Here, we examined 211 field plots in boreal forests dominated by black spruce ( Picea mariana ) or jack pine ( Pinus banksiana ) of the Northwest Territories ( NWT ), Canada after an unprecedentedly large area burned in 2014. We assessed both aboveground and soil organic layer ( SOL ) combustion, with the goal of determining the major drivers in total C emissions, as well as to develop a high spatial resolution model to scale emissions in a relatively understudied region of the boreal forest. On average, 3.35 kg C m −2 was combusted and almost 90% of this was from SOL combustion. Our results indicate that black spruce stands located at landscape positions with intermediate drainage contribute the most to C emissions. Indices associated with fire weather and date of burn did not impact emissions, which we attribute to the extreme fire weather over a short period of time. Using these results, we estimated a total of 94.3 Tg C emitted from 2.85 Mha of burned area across the entire 2014 NWT fire complex, which offsets almost 50% of mean annual net ecosystem production in terrestrial ecosystems of Canada. Our study also highlights the need for fine‐scale estimates of burned area that represent small water bodies and regionally specific calibrations of combustion that account for spatial heterogeneity in order to accurately model emissions at the continental scale.

Ecology can inform genetics: Disassortative mating contributes to MHC polymorphism in Leach’s storm‐petrels ( Oceanodroma leucorhoa ) - Brian Hoover; Miguel Alcaide; Sarah Jennings; Simon Yung Wa Sin; Scott V. Edwards; Gabrielle A. Nevitt (Molecular Ecology, 2018)
Studies of MHC‐based mate choice in wild populations often test hypotheses on species exhibiting female choice and male–male competition, which reflects the general prevalence of females as the choosy sex in natural systems. Here, we examined mutual mate‐choice patterns in a small burrow‐nesting seabird, the Leach’s storm‐petrel ( Oceanodroma leucorhoa ), using the major histocompatibility complex (MHC). The life history and ecology of this species are extreme: both partners work together to fledge a single chick during the breeding season, a task that requires regularly travelling hundreds of kilometres to and from foraging grounds over a 6‐ to 8‐week provisioning period. Using a 5‐year data set unprecedented for this species ( n = 1078 adults and 925 chicks), we found a positive relationship between variation in the likelihood of female reproductive success and heterozygosity at Ocle‐ DAB 2, a MHC class IIB locus. Contrary to previous reports rejecting disassortative mating as a mechanism for maintaining genetic polymorphism in this species, here we show that males make significant disassortative mate‐choice decisions. Variability in female reproductive success suggests that the most common homozygous females (Ocle‐ DAB 2*01/Ocle‐ DAB 2*01) may be physiologically disadvantaged and, therefore, less preferred as lifelong partners for choosy males. The results from this study support the role of mate choice in maintaining high levels of MHC variability in a wild seabird species and highlight the need to incorporate a broader ecological framework and sufficient sample sizes into studies of MHC ‐based mating patterns in wild populations in general.

Long-term grazing impacts on vegetation diversity, composition, and exotic species presence across an aridity gradient in northern temperate grasslands - Mark P. Lyseng; Edward W. Bork; Daniel B. Hewins; Mike J. Alexander; Cameron N. Carlyle; Scott X. Chang; Walter D. Willms (Plant Ecology, 2018)

Comparative, collaborative, and integrative risk governance for emerging technologies - Igor Linkov; Benjamin D. Trump; Elke Anklam; David Berube; Patrick Boisseasu; Christopher Cummings; Scott Ferson; Marie-Valentine Florin; Bernard Goldstein; Danail Hristozov; Keld Alstrup Jensen; Georgios Katalagarianakis; et al. (Environment Systems and Decisions, 2018)

Detecting early warning signals of tree mortality in boreal North America using multiscale satellite data - Brendan M. Rogers; Kylen Solvik; Edward H. Hogg; Junchang Ju; Jeffrey G. Masek; Michael Michaelian; Logan T. Berner; Scott J. Goetz (Global Change Biology, 2018)
Increasing tree mortality from global change drivers such as drought and biotic infestations is a widespread phenomenon, including in the boreal zone where climate changes and feedbacks to the Earth system are relatively large. Despite the importance for science and management communities, our ability to forecast tree mortality at landscape to continental scales is limited. However, two independent information streams have the potential to inform and improve mortality forecasts: repeat forest inventories and satellite remote sensing. Time series of tree‐level growth patterns indicate that productivity declines and related temporal dynamics often precede mortality years to decades before death. Plot‐level productivity, in turn, has been related to satellite‐based indices such as the Normalized difference vegetation index ( NDVI ). Here we link these two data sources to show that early warning signals of mortality are evident in several NDVI ‐based metrics up to 24 years before death. We focus on two repeat forest inventories and three NDVI products across western boreal North America where productivity and mortality dynamics are influenced by periodic drought. These data sources capture a range of forest conditions and spatial resolution to highlight the sensitivity and limitations of our approach. Overall, results indicate potential to use satellite NDVI for early warning signals of mortality. Relationships are broadly consistent across inventories, species, and spatial resolutions, although the utility of coarse‐scale imagery in the heterogeneous aspen parkland was limited. Longer‐term NDVI data and annually remeasured sites with high mortality levels generate the strongest signals, although we still found robust relationships at sites remeasured at a typical 5 year frequency. The approach and relationships developed here can be used as a basis for improving forest mortality models and monitoring systems.

Physiological and regulatory underpinnings of geographic variation in reptilian cold tolerance across a latitudinal cline - Shane C. Campbell‐Staton; Anna Bare; Jonathan B. Losos; Scott V. Edwards; Zachary A. Cheviron (Molecular Ecology, 2018)
Understanding the mechanisms that produce variation in thermal performance is a key component to investigating climatic effects on evolution and adaptation. However, disentangling the effects of local adaptation and phenotypic plasticity in shaping patterns of geographic variation in natural populations can prove challenging. Additionally, the physiological mechanisms that cause organismal dysfunction at extreme temperatures are still largely under debate. Using the green anole, Anolis carolinensis , we integrate measures of cold tolerance ( CT min ), standard metabolic rate, heart size, blood lactate concentration and RNA seq data from liver tissue to investigate geographic variation in cold tolerance and its underlying mechanisms along a latitudinal cline. We found significant effects of thermal acclimation and latitude of origin on variation in cold tolerance. Increased cold tolerance correlates with decreased rates of oxygen consumption and blood lactate concentration (a proxy for oxygen limitation), suggesting elevated performance is associated with improved oxygen economy during cold exposure. Consistent with these results, co‐expression modules associated with blood lactate concentration are enriched for functions associated with blood circulation, coagulation and clotting. Expression of these modules correlates with thermal acclimation and latitude of origin. Our findings support the oxygen and capacity‐limited thermal tolerance hypothesis as a potential contributor to variation in reptilian cold tolerance. Moreover, differences in gene expression suggest regulation of the blood coagulation cascade may play an important role in reptilian cold tolerance and may be the target of natural selection in populations inhabiting colder environments.

The phase diagrams of KCaF3 and NaMgF3 by ab initio simulations - Clément Jakymiw; Lidunka Vočadlo; David P. Dobson; Edward Bailey; Andrew R. Thomson; John P. Brodholt; Ian G. Wood; Alex Lindsay-Scott (Physics and Chemistry of Minerals, 2018)

Treatment and survival disparities by ethnicity in New Zealand women with stage I–III breast cancer tumour subtypes - Ross Lawrenson; Chunhuan Lao; Ian Campbell; Vernon Harvey; Sanjeewa Seneviratne; Melissa Edwards; Mark Elwood; Nina Scott; Jacquie Kidd; Diana Sarfati; Marion Kuper-Hommel (Cancer Causes & Control, 2017)

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Erratum to: A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)

A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)
Uterine fibroids are benign tumors of the uterus affecting up to 77% of women by menopause. They are the leading indication for hysterectomy, and account for $34 billion annually in the United States. Race/ethnicity and age are the strongest known risk factors. African American (AA) women have higher prevalence, earlier onset, and larger and more numerous fibroids than European American women. We conducted a multi-stage genome-wide association study (GWAS) of fibroid risk among AA women followed by in silico genetically predicted gene expression profiling of top hits. In Stage 1, cases and controls were confirmed by pelvic imaging, genotyped and imputed to 1000 Genomes. Stage 2 used self-reported fibroid and GWAS data from 23andMe, Inc. and the Black Women’s Health Study. Associations with fibroid risk were modeled using logistic regression adjusted for principal components, followed by meta-analysis of results. We observed a significant association among 3399 AA cases and 4764 AA controls at rs739187 (risk-allele frequency = 0.27) in CYTH4 (OR (95% confidence interval) = 1.23 (1.16–1.30), p value = 7.82 × 10 −9 ). Evaluation of the genetic association results with MetaXcan identified lower predicted gene expression of CYTH4 in thyroid tissue as significantly associated with fibroid risk ( p value = 5.86 × 10 −8 ). In this first multi-stage GWAS for fibroids among AA women, we identified a novel risk locus for fibroids within CYTH4 that impacts gene expression in thyroid and has potential biological relevance for fibroids.

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

Genomic footprints of adaptation in a cooperatively breeding tropical bird across a vegetation gradient - Flavia Termignoni‐García; Juan P. Jaramillo‐Correa; Juan Chablé‐Santos; Mark Liu; Allison J. Shultz; Scott V. Edwards; Patricia Escalante‐Pliego (Molecular Ecology, 2017)
Identifying the genetic basis of phenotypic variation and its relationship with the environment is key to understanding how local adaptations evolve. Such patterns are especially interesting among populations distributed across habitat gradients, where genetic structure can be driven by isolation by distance ( IBD ) and/or isolation by environment ( IBE ). Here, we used variation in ~1,600 high‐quality SNP s derived from paired‐end sequencing of double‐digest restriction site‐associated DNA (dd RAD ‐Seq) to test hypotheses related to IBD and IBE in the Yucatan jay ( Cyanocorax yucatanicus) , a tropical bird endemic to the Yucatán Peninsula. This peninsula is characterized by a precipitation and vegetation gradient—from dry to evergreen tropical forests—that is associated with morphological variation in this species. We found a moderate level of nucleotide diversity (π = .008) and little evidence for genetic differentiation among vegetation types. Analyses of neutral and putatively adaptive SNP s (identified by complementary genome‐scan approaches) indicate that IBD is the most reliable explanation to account for frequency distribution of the former, while IBE has to be invoked to explain those of the later. These results suggest that selective factors acting along a vegetation gradient can promote local adaptation in the presence of gene flow in a vagile, nonmigratory and geographically restricted species. The putative candidate SNP s identified here are located within or linked to a variety of genes that represent ideal targets for future genomic surveys.

Elemental composition of Malawian rice - Edward J. M. Joy; E. Louise Ander; Martin R. Broadley; Scott D. Young; Allan D. C. Chilimba; Elliott M. Hamilton; Michael J. Watts (Environmental Geochemistry and Health, 2017)

Litter decay controlled by temperature, not soil properties, affecting future soil carbon - Edward G. Gregorich; Henry Janzen; Benjamin H. Ellert; Bobbi L. Helgason; Budong Qian; Bernie J. Zebarth; Denis A. Angers; Ronald P. Beyaert; Craig F. Drury; Scott D. Duguid; William E. May; Brian G. McConkey; et al. (Global Change Biology, 2017)
Widespread global changes, including rising atmospheric CO 2 concentrations, climate warming and loss of biodiversity, are predicted for this century; all of these will affect terrestrial ecosystem processes like plant litter decomposition. Conversely, increased plant litter decomposition can have potential carbon‐cycle feedbacks on atmospheric CO 2 levels, climate warming and biodiversity. But predicting litter decomposition is difficult because of many interacting factors related to the chemical, physical and biological properties of soil, as well as to climate and agricultural management practices. We applied 13 C‐labelled plant litter to soil at ten sites spanning a 3500‐km transect across the agricultural regions of Canada and measured its decomposition over five years. Despite large differences in soil type and climatic conditions, we found that the kinetics of litter decomposition were similar once the effect of temperature had been removed, indicating no measurable effect of soil properties. A two‐pool exponential decay model expressing undecomposed carbon simply as a function of thermal time accurately described kinetics of decomposition. ( R 2 = 0.94; RMSE = 0.0508). Soil properties such as texture, cation exchange capacity, pH and moisture, although very different among sites, had minimal discernible influence on decomposition kinetics. Using this kinetic model under different climate change scenarios, we projected that the time required to decompose 50% of the litter (i.e. the labile fractions) would be reduced by 1–4 months, whereas time required to decompose 90% of the litter (including recalcitrant fractions) would be reduced by 1 year in cooler sites to as much as 2 years in warmer sites. These findings confirm quantitatively the sensitivity of litter decomposition to temperature increases and demonstrate how climate change may constrain future soil carbon storage, an effect apparently not influenced by soil properties.

Valuing increased zinc (Zn) fertiliser-use in Pakistan - Edward J. M. Joy; Waqar Ahmad; Munir H. Zia; Diriba B. Kumssa; Scott D. Young; E. Louise Ander; Michael J. Watts; Alexander J. Stein; Martin R. Broadley (Plant and Soil, 2017)

Ecosystem responses to climate change at a Low Arctic and a High Arctic long-term research site - John E. Hobbie; Gaius R. Shaver; Edward B. Rastetter; Jessica E. Cherry; Scott J. Goetz; Kevin C. Guay; William A. Gould; George W. Kling (Ambio, 2017)

Alcohol dependence-induced regulation of the proliferation and survival of adult brain progenitors is associated with altered BDNF-TrkB signaling - Sucharita S. Somkuwar; McKenzie J. Fannon; Miranda C. Staples; Eva R. Zamora-Martinez; Alvaro I. Navarro; Airee Kim; Jacqueline A. Quigley; Scott Edwards; Chitra D. Mandyam (Brain Structure and Function, 2016)

Watering increased DOC concentration but decreased N2O emission from a mixed grassland soil under different defoliation regimes - Yanjiang Cai; Scott X. Chang; Bin Ma; Edward W. Bork (Biology and Fertility of Soils, 2016)

Phylogenomic subsampling: a brief review - Scott V. Edwards (Zoologica Scripta, 2016)
Phylogenomic subsampling is a method for studying the stability of phylogenetic analyses by taking random or ordered subsamples of loci and comparing phylogenetic analyses of those subsamples. The method is made possible by the large number of loci made available by application of next‐generation sequencing methods to phylogenetic questions. My laboratory has used phylogenomic subsampling to investigate the consistency and stability of various methods of phylogenetic analysis of multilocus data sets, including the so‐called species tree methods, which use the multispecies coalescent as a framework for interpreting gene tree heterogeneity. I was inspired to focus on this method for this symposium volume because my Harvard colleague Gonzalo Giribet had independently been using phylogenomic subsampling to explore various questions in invertebrate phylogenomics. Phylogenomic subsampling has many useful applications in phylogenomics, yet when reporting the particulars of the results of such analyses, care should be taken to focus primarily on discrepancies that achieve a high level of support by the bootstrap or other methods. Using a recently published example, I show that the methods used to summarize the results of a subsampling experiment, such as the threshold for reporting support for one or another tree or clade, can influence the perceived success or failure of concatenation or species tree methods. Single‐ versus double‐bootstrapping is also shown to produce different subsampling results. I suggest guidelines for analysing and reporting the results of phylogenomic subsampling and suggest that it should become a routine part of phylogenetic analysis in the next‐generation era.

Chemical Composition of Macondo and Other Crude Oils and Compositional Alterations During Oil Spills - Edward Overton; Terry Wade; Jagoit Radovic; Buffy Meyer; M. Scott Miles; Stephen Larter (Oceanography, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Sub-canopy Evapotranspiration from Floating Vegetation and Open Water in a Swamp Forest - Scott T. Allen; Brandon L. Edwards; Michele L. Reba; Richard F. Keim (Wetlands, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

A conceptual framework for analyzing deltas as coupled social–ecological systems: an example from the Amazon River Delta - Eduardo S. Brondizio; Nathan D. Vogt; Andressa V. Mansur; Edward J. Anthony; Sandra Costa; Scott Hetrick (Sustainability Science, 2016)

Determinants of bacterial communities in C anadian agroforestry systems - Samiran Banerjee; Mark Baah‐Acheamfour; Cameron N. Carlyle; Andrew Bissett; Alan E. Richardson; Tariq Siddique; Edward W. Bork; Scott X. Chang (Environmental Microbiology, 2016)
Summary Land‐use change is one of the most important factors influencing soil microbial communities, which play a pivotal role in most biogeochemical and ecological processes. Using agroforestry systems as a model, this study examined the effects of land uses and edaphic properties on bacterial communities in three agroforestry types covering a 270 km soil‐climate gradient in A lberta, C anada. Our results demonstrate that land‐use patterns exert stronger effects on soil bacterial communities than soil zones in these agroforestry systems. Plots with trees in agroforestry systems promoted greater bacterial abundance and to some extent species richness, which was associated with more nutrient‐rich soil resources. While A cidobacteria , A ctinobacteria and A lphaproteobacteria were the dominant bacterial phyla and subphyla across land uses, A rthrobacter , A cidobacteria_ G p16 , B urkholderia , R hodanobacter and R hizobium were the keystone taxa in these agroforestry systems. Soil pH and carbon contents emerged as the major determinants of bacterial community characteristics. We found non‐random co‐occurrence and modular patterns of soil bacterial communities, and these patterns were controlled by edaphic factors and not their taxonomy. Overall, this study highlights the drivers and co‐occurrence patterns of soil microbial communities in agroforestry systems.

Shrubline but not treeline advance matches climate velocity in montane ecosystems of south‐central Alaska - Roman J. Dial; T. Scott Smeltz; Patrick F. Sullivan; Christina L. Rinas; Katriina Timm; Jason E. Geck; S. Carl Tobin; Trevor S. Golden; Edward C. Berg (Global Change Biology, 2016)
Tall shrubs and trees are advancing into many tundra and wetland ecosystems but at a rate that often falls short of that predicted due to climate change. For forest, tall shrub, and tundra ecosystems in two pristine mountain ranges of Alaska, we apply a Bayesian, error‐propagated calculation of expected elevational rise (climate velocity), observed rise (biotic velocity), and their difference (biotic inertia). We show a sensitive dependence of climate velocity on lapse rate and derive biotic velocity as a rigid elevational shift. Ecosystem presence identified from recent and historic orthophotos ~50 years apart was regressed on elevation. Biotic velocity was estimated as the difference between critical point elevations of recent and historic logistic fits divided by time between imagery. For both mountain ranges, the 95% highest posterior density of climate velocity enclosed the posterior distributions of all biotic velocities. In the Kenai Mountains, mean tall shrub and climate velocities were both 2.8 m y −1 . In the better sampled Chugach Mountains, mean tundra retreat was 1.2 m y −1 and climate velocity 1.3 m y −1 . In each mountain range, the posterior mode of tall woody vegetation velocity (the complement of tundra) matched climate velocity better than either forest or tall shrub alone, suggesting competitive compensation can be important. Forest velocity was consistently low at 0.1–1.1 m y −1 , indicating treeline is advancing slowly. We hypothesize that the high biotic inertia of forest ecosystems in south‐central Alaska may be due to competition with tall shrubs and/or more complex climate controls on the elevational limits of trees than tall shrubs. Among tall shrubs, those that disperse farthest had lowest inertia. Finally, the rapid upward advance of woody vegetation may be contributing to regional declines in Dall's sheep (Ovis dalli), a poorly dispersing alpine specialist herbivore with substantial biotic inertia due to dispersal reluctance.

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Polyaromatic hydrocarbons and elements in sediments associated with a suburban railway - Jeffrey M. Levengood; Edward J. Heske; Patrick M. Wilkins; John W. Scott (Environmental Monitoring and Assessment, 2015)

Structural reorganization of pyramidal neurons in the medial prefrontal cortex of alcohol dependent rats is associated with altered glial plasticity - Airee Kim; Eva R. Zamora-Martinez; Scott Edwards; Chitra D. Mandyam (Brain Structure and Function, 2015)

Zinc-enriched fertilisers as a potential public health intervention in Africa - Edward J. M. Joy; Alexander J. Stein; Scott D. Young; E. Louise Ander; Michael J. Watts; Martin R. Broadley (Plant and Soil, 2015)

Design Control for Clinical Translation of 3D Printed Modular Scaffolds - Scott J. Hollister; Colleen L. Flanagan; David A. Zopf; Robert J. Morrison; Hassan Nasser; Janki J. Patel; Edward Ebramzadeh; Sophia N. Sangiorgio; Matthew B. Wheeler; Glenn E. Green (Annals of Biomedical Engineering, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Admixture mapping identifies a locus at 15q21.2–22.3 associated with keloid formation in African Americans - Digna R. Velez Edwards; Krystal S. Tsosie; Scott M. Williams; Todd L. Edwards; Shirley B. Russell (Human Genetics, 2014)

Constraints on post‐glacial boreal tree expansion out of far‐northern refugia - Mary E. Edwards; W. Scott Armbruster; Scott E. Elias (Global Ecology and Biogeography, 2014)
Aim To use a variety of data sources to infer how northern boreal trees recovered their range upon deglaciation and/or H olocene warming. Location Scandinavia, A laska/north‐west C anada (eastern B eringia). Methods Mapped fossil occurrences for P icea (spruce) were assessed against available palaeoenvironmental and phylogeographic information. Results For S candinavia, L ast G lacial M aximum ( LGM ) evidence of P icea is confined to one DNA record, but late‐glacial and early‐Holocene records include scattered macrofossils. Holocene pollen data show a clear east–west increase to high values. A haplotype unique to the S candinavian P eninsula is recognized. For eastern B eringia pre‐ and post‐ LGM macrofossils occur, but the LGM fossil record comprises only scattered low pollen values. Early H olocene pollen values increase markedly c . 11 cal yr bp (north‐west C anada) and c . 10 kcal yr bp (central A laska). Also at this time three sites on the B ering L and B ridge indicate the presence of P icea where it is now absent. Several unique regional haplotypes were recorded; while most are rare one is common in some modern populations. Main conclusions Small P icea populations probably occurred in pre‐ H olocene S candinavia, but pollen patterns argue against immediate expansion with the onset of warmer conditions. Despite relatively weak fossil evidence, refugial populations are also probable in eastern B eringia, particularly given the extent of unglaciated terrain. Post‐glacial pollen patterns are more nuanced, suggesting two spatially and temporally distinct expansions, one possibly consistent with a unique central A laskan haplotype, and subsequent westerly ‘filling‐in’. The presence of macrofossils and/or neutral markers does not require that current northern populations are derived primarily from refugial ones, particularly where pollen patterns show delayed directional expansion of large populations though time. Refugial populations initially responded weakly to major post‐glacial environmental change; if subject to genetic isolation and strong selection pressure they may have had little potential to do otherwise, instead being largely replaced by in‐migrating populations with greater genetic diversity.

Resolving the Beaufort Sea High using synoptic climatological methods - Thomas J. Ballinger; Scott C. Sheridan; Edward Hanna (International Journal of Climatology, 2014)
Melt season frequencies of the Beaufort Sea High ( BSH ) have a profound effect on western Arctic climate, making the interannual spatial and temporal monitoring of this polar anticyclone important. This manuscript presents two automated synoptic climatological analyses using a two‐step cluster procedure to classify daily mean sea level pressure ( MSLP ) over 180–120°W and 70–85°N with an emphasis on identifying BSH patterns. Separate raw and anomaly MSLP circulation pattern ( CP ) classifications are compared in order to assess the spatial characteristics of the BSH and its monthly frequency changes during the melt season from 1979 to 2012. Analysis of both classifications shows clear advantages to using the anomaly approach in terms of assessing temporal and spatial changes, particularly in light of the documented recent atmospheric circulation changes that have been observed over the region. Associations between the June anomaly circulation pattern ( ACP ) 5, a +4 hPa BSH pattern situated between 155°W and 135°W, and June indices of atmospheric teleconnections such as the Arctic Dipole and Arctic Oscillation are statistically significant. There is also a statistically significant link to the downstream Greenland Blocking Index; suggesting that the BSH may be intricately related to climatic variability outside the analysed domain as well. Further, ACP 5 occurred nearly 3 weeks more often during the melt season in recent massive Arctic Sea ice loss years (2007–2012) compared with the climatology (1979–2006). Recent increases in June ACP 5 frequencies account for a large proportion of this pattern's long‐term frequency changes.

Tundra and boreal forest of interior Alaska during terminal MIS 6 and MIS 5e - Nancy H. Bigelow; Mary E. Edwards; Scott A. Elias; Thomas D. Hamilton; Charles E. Schweger (Vegetation History and Archaeobotany, 2014)

Interactions of time of day and sleep with between-session habituation and extinction memory in young adult males - Edward F. Pace-Schott; Lauren E. Tracy; Zoe Rubin; Adrian G. Mollica; Jeffrey M. Ellenbogen; Matt T. Bianchi; Mohammed R. Milad; Roger K. Pitman; Scott P. Orr (Experimental Brain Research, 2014)

Detection of geophysical features in InSAR point cloud data sets using spatiotemporal models - Andrea Vaccari; Michael Stuecheli; Brian Bruckno; Edward Hoppe; Scott T. Acton (International Journal of Remote Sensing, 2013)

Parkinson disease loci in the mid-western Amish - M. F. Davis; A. C. Cummings; L. N. D’Aoust; L. Jiang; D. R. Velez Edwards; R. Laux; L. Reinhart-Mercer; D. Fuzzell; W. K. Scott; M. A. Pericak-Vance; S. L. Lee; J. L. Haines (Human Genetics, 2013)

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Multilocus tests of P leistocene refugia and ancient divergence in a pair of A tlantic F orest antbirds ( M yrmeciza ) - Fábio Raposo do Amaral; Patrick K. Albers; Scott V. Edwards; Cristina Y. Miyaki (Molecular Ecology, 2013)
The Atlantic Forest (AF) harbours one of the most diverse vertebrate faunas of the world, including 199 endemic species of birds. Understanding the evolutionary processes behind such diversity has become the focus of many recent, primarily single locus, phylogeographic studies. These studies suggest that isolation in forest refugia may have been a major mechanism promoting diversification, although there is also support for a role of riverine and geotectonic barriers, two sets of hypotheses that can best be tested with multilocus data. Here we combined multilocus data (one mtDNA marker and eight anonymous nuclear loci) from two species of parapatric antbirds, M yrmeciza loricata and M. squamosa , and Approximate B ayesian Computation to determine whether isolation in refugia explains current patterns of genetic variation and their status as independent evolutionary units. Patterns of population structure, differences in intraspecific levels of divergence and coalescent estimates of historical demography fit the predictions of a recently proposed model of refuge isolation in which climatic stability in the northern AF sustains higher diversity and demographic stability than in the southern AF. However, a pre‐Pleistocene divergence associated with their abutting range limits in a region of past tectonic activity also suggests a role for rivers or geotectonic barriers. Little or no gene flow between these species suggests the development of reproductive barriers or competitive exclusion. Our results suggests that limited marker sampling in recent AF studies may compromise estimates of divergence times and historical demography, and we discuss the effects of such sampling on this and other studies.

Next‐generation QTL mapping: crowdsourcing SNP s, without pedigrees - Scott V. Edwards (Molecular Ecology, 2013)
For many molecular ecologists, the mantra and mission of the field of ecological genomics could be encapsulated by the phrase ‘to find the genes that matter’ (Mitchell‐Olds ; Rockman ). This phrase of course refers to the early hope and current increasing success in the search for genes whose variation underlies phenotypic variation and fitness in natural populations. In the years since the modern incarnation of the field of ecological genomics, many would agree that the low‐hanging fruit has, at least in principle, been plucked: we now have several elegant examples of genes whose variation influences key adaptive traits in natural populations, and these examples have revealed important insights into the architecture of adaptive variation (Hoekstra et al . ; Shapiro et al . ; Chan et al . ). But how well will these early examples, often involving single genes of large effect on discrete or near‐discrete phenotypes, represent the dynamics of adaptive change for the totality of phenotypes in nature? Will traits exhibiting continuous rather than discrete variation in natural populations have as simple a genetic basis as these early examples suggest (Prasad et al . ; Rockman )? Two papers in this issue (Robinson et al . ; Santure et al . ) not only suggest answers to these questions but also provide useful extensions of statistical approaches for ecological geneticists to study the genetics of continuous variation in nature. Together these papers, by the same research groups studying evolution in a natural population of G reat T its ( P arus major ), provide a glimpse of what we should expect as the field begins to dissect the genetic basis of what is arguably the most common type of variation in nature, and how genome‐wide surveys of variation can be applied to natural populations without pedigrees.

Risk of dietary magnesium deficiency is low in most African countries based on food supply data - Edward J. M. Joy; Scott D. Young; Colin R. Black; E. Louise Ander; Michael J. Watts; Martin R. Broadley (Plant and Soil, 2013)

Estimating global arthropod species richness: refining probabilistic models using probability bounds analysis - Andrew J. Hamilton; Vojtech Novotný; Edward K. Waters; Yves Basset; Kurt K. Benke; Peter S. Grimbacher; Scott E. Miller; G. Allan Samuelson; George D. Weiblen; Jian D. L. Yen; Nigel E. Stork (Oecologia, 2013)

Erratum to: Landscape-Scale Factors Affecting Feral Horse Habitat Use During Summer Within The Rocky Mountain Foothills - Tisa L. Girard; Edward W. Bork; Scott E. Nielsen; Mike J. Alexander (Environmental Management, 2013)

Landscape-Scale Factors Affecting Feral Horse Habitat Use During Summer Within The Rocky Mountain Foothills - Tisa L. Girard; Edward W. Bork; Scott E. Neilsen; Mike J. Alexander (Environmental Management, 2013)

Age-dependent molecular alterations in the autophagy pathway in HIVE patients and in a gp120 tg mouse model: reversal with beclin-1 gene transfer - Jerel Fields; Wilmar Dumaop; Edward Rockenstein; Michael Mante; Brian Spencer; Igor Grant; Ron Ellis; Scott Letendre; Christina Patrick; Anthony Adame; Eliezer Masliah (Journal of NeuroVirology, 2013)

Toxicity of sediment pore water in Puget Sound (Washington, USA): a review of spatial status and temporal trends - Edward R. Long; R. Scott Carr; James M. Biedenbach; Sandra Weakland; Valerie Partridge; Margaret Dutch (Environmental Monitoring and Assessment, 2013)

Steady‐state bioassay approach applied to phosphorus‐limited continuous cultures: A growth study of the marine chlorophyte Dunaliella salina - Scott R. Grant; Paul K. Bienfang; Edward A. Laws (Limnology and Oceanography, 2013)
Phosphorus‐limited growth and phosphate uptake kinetics of the marine phytoplankter Dunaliella salina were studied using continuous‐culture techniques. Determination of residual phosphate concentrations in the cultures were made using a steady‐state bioassay approach in which short‐term phosphate uptake rates as measured by 33 P‐radiotracer were balanced with the turnover of phosphorus in the culture. This allowed the determination of low‐nanomolar ambient phosphate concentrations (8–95 nmol P L −1 ) at seven unique specific growth rates, which agreed closely with an alternative kinetics bioassay phosphate determination. The relationship of specific growth rate to ambient phosphate concentration for the D. salina cultures was well‐described by the Monod growth equation with μ max = 1.8 d −1 and K μ = 28 nmol P L −1 . Phosphate uptake kinetics were evaluated at three growth rates and adhered to Michaelis‐Menten kinetics, with evidence of growth‐rate‐dependent variability of uptake affinities (1.9–3.0 L µmol −1 h −1 ) and half‐saturation constants (1.85–3.8 µmol P L −1 ). Maximum uptake rates were constant across growth rates when measured in either carbon‐specific (220 µmol P mol C −1 min −1 ), volume‐specific (7 amol P µm −3 min −1 ), cell‐specific (1 fmol P cell −1 min −1 ), or phosphorus‐specific units (7 h −1 ). This represents a phosphate uptake rate capacity between 200‐fold and 600‐fold greater than the requirements for growth. Finally, we compared the results from our study with previous studies across four phytoplankton species and found that the Monod half‐saturation constant for phosphorus‐limited growth ( K μ ) is well‐predicted by the theoretical ratio of the maximum specific growth rate to the phosphorus‐specific uptake affinity.

High gene flow on a continental scale in the polyandrous K entish plover C haradrius alexandrinus - Clemens Küpper; Scott V. Edwards; András Kosztolányi; Monif Alrashidi; Terry Burke; Philipp Herrmann; Araceli Argüelles‐Tico; Juan A. Amat; Mohamed Amezian; Afonso Rocha; Hermann Hötker; Anton Ivanov; et al. (Molecular Ecology, 2012)
Gene flow promotes genetic homogeneity of species in time and space. Gene flow can be modulated by sex‐biased dispersal that links population genetics to mating systems. We investigated the phylogeography of the widely distributed K entish plover C haradrius alexandrinus . This small shorebird has a large breeding range spanning from W estern E urope to J apan and exhibits an unusually flexible mating system with high female breeding dispersal. We analysed genetic structure and gene flow using a 427‐bp fragment of the mitochondrial (mt DNA ) control region, 21 autosomal microsatellite markers and a Z microsatellite marker in 397 unrelated individuals from 21 locations. We found no structure or isolation‐by‐distance over the continental range. However, island populations had low genetic diversity and were moderately differentiated from mainland locations. Genetic differentiation based on autosomal markers was positively correlated with distance between mainland and each island. Comparisons of uniparentally and biparentally inherited markers were consistent with female‐biased gene flow. Maternally inherited mt DNA was less structured, whereas the Z ‐chromosomal marker was more structured than autosomal microsatellites. Adult males were more related than females within genetic clusters. Taken together, our results suggest a prominent role for polyandrous females in maintaining genetic homogeneity across large geographic distances.

Integrating Climate and Ocean Change Vulnerability into Conservation Planning - Elizabeth McLeod; Alison Green; Edward Game; Kenneth Anthony; Joshua Cinner; Scott F. Heron; Joanie Kleypas; Catherine E. Lovelock; John M. Pandolfi; Robert L. Pressey; Rodney Salm; Steve Schill; et al. (Coastal Management, 2012)

Regular dental visits are associated with earlier stage at diagnosis for oral and pharyngeal cancer - Scott M. Langevin; Dominique S. Michaud; Melissa Eliot; Edward S. Peters; Michael D. McClean; Karl T. Kelsey (Cancer Causes & Control, 2012)

Gene expression changes of interconnected spared cortical neurons 7 days after ischemic infarct of the primary motor cortex in the rat - Edward T. R. Urban; Scott D. Bury; H. Scott Barbay; David J. Guggenmos; Yafeng Dong; Randolph J. Nudo (Molecular and Cellular Biochemistry, 2012)

Eight anonymous nuclear loci for the squamate antbird (Myrmeciza squamosa), cross-amplifiable in other species of typical antbirds (Aves, Thamnophilidae) - Fábio Raposo do Amaral; Scott V. Edwards; Cristina Y. Miyaki (Conservation Genetics Resources, 2012)

Editorial of the Proceedings of the 25th International Ornithological Congress - John Wingfield; Scott Edwards; Cristina Miyaki (Journal of Ornithology, 2012)

Estimates of surface drifter trajectories in the equatorial Atlantic: a multi-model ensemble approach - Robert Bruce Scott; Nicolas Ferry; Marie Drévillon; Charlie N. Barron; Nicolas C. Jourdain; Jean-Michel Lellouche; Edward Joseph Metzger; Marie-Hélène Rio; Ole Martin Smedstad (Ocean Dynamics, 2012)

Innate immunity and the evolution of resistance to an emerging infectious disease in a wild bird - CAMILLE BONNEAUD; SUSAN L. BALENGER; JIANGWEN ZHANG; SCOTT V. EDWARDS; GEOFFREY E. HILL (Molecular Ecology, 2012)
Innate immunity is expected to play a primary role in conferring resistance to novel infectious diseases, but few studies have attempted to examine its role in the evolution of resistance to emerging pathogens in wild vertebrate populations. Here, we used experimental infections and cDNA microarrays to examine whether changes in the innate and/or acquired immune responses likely accompanied the emergence of resistance in house finches ( Carpodacus mexicanus ) in the eastern United States subject to a recent outbreak of conjunctivitis‐causing bacterium ( Mycoplasma gallisepticum —MG). Three days following experimental infection with MG, we observed differences in the splenic transcriptional responses between house finches from eastern U.S. populations, with a 12‐year history of MG exposure, versus western U.S. populations, with no history of exposure to MG. In particular, western birds down‐regulated gene expression, while eastern finches showed no expression change relative to controls. Studies involving poultry have shown that MG can manipulate host immunity, and our observations suggest that pathogen manipulation occurred only in finches from the western populations, outside the range of MG. Fourteen days after infection, eastern finches, but not western finches, up‐regulated genes associated with acquired immunity (cell‐mediated immunity) relative to controls. These observations suggest population differences in the temporal course of the response to infection with MG and imply that innate immune processes were targets of selection in response to MG in the eastern U.S. population.

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Polyandry and multiple paternities in the threatened Agassiz’s desert tortoise, Gopherus agassizii - Christina M. Davy; Taylor Edwards; Amy Lathrop; Mark Bratton; Mark Hagan; Brian Henen; Kenneth A. Nagy; Jonathon Stone; L. Scott Hillard; Robert W. Murphy (Conservation Genetics, 2011)

RETRACTED ARTICLE: Neurotoxic effects of the HCV core protein are mediated by sustained activation of ERK via TLR2 signaling - Amy D. Paulino; Kiren Ubhi; Edward Rockenstein; Anthony Adame; Leslie Crews; Scott Letendre; Ronald Ellis; Ian P. Everall; Igor Grant; Eliezer Masliah (Journal of NeuroVirology, 2011)

Validity of the Actical for estimating free-living physical activity - Scott E. Crouter; Diane M. DellaValle; Magdalene Horton; Jere D. Haas; Edward A. Frongillo; David R. Bassett (European Journal of Applied Physiology, 2011)

CyberShake: A Physics-Based Seismic Hazard Model for Southern California - Robert Graves; Thomas H. Jordan; Scott Callaghan; Ewa Deelman; Edward Field; Gideon Juve; Carl Kesselman; Philip Maechling; Gaurang Mehta; Kevin Milner; David Okaya; Patrick Small; et al. (Pure and Applied Geophysics, 2011)

Scaling an Instantaneous Model of Tundra NEE to the Arctic Landscape - Michael M. Loranty; Scott J. Goetz; Edward B. Rastetter; Adrian V. Rocha; Gaius R. Shaver; Elyn R. Humphreys; Peter M. Lafleur (Ecosystems, 2011)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)

Specificity between Neotropical tree seedlings and their fungal mutualists leads to plant–soil feedback - Scott A. Mangan; Edward A. Herre; James D. Bever (Ecology, 2010)
A growing body of evidence obtained largely from temperate grassland studies suggests that feedbacks occurring between plants and their associated soil biota are important to plant community assemblage. However, few studies have examined the importance of soil organisms in driving plant–soil feedbacks in forested systems. In a tropical forest in central Panama, we examined whether interactions between tree seedlings and their associated arbuscular mycorrhizal fungi (AMF) lead to plant–soil feedback. Specifically, do tropical seedlings modify their own AMF communities in a manner that either favors or inhibits the next cohort of conspecific seedlings (i.e., positive or negative feedback, respectively)? Seedlings of two shade‐tolerant tree species ( Eugenia nesiotica , Virola surinamensis ) and two pioneer tree species ( Luehea seemannii , Apeiba aspera ) were grown in pots containing identical AMF communities composed of equal amounts of inoculum of six co‐occurring AMF species. The different AMF–host combinations were all exposed to two light levels. Under low light (2% PAR), only two of the six AMF species sporulated, and we found that host identity did not influence composition of AMF spore communities. However, relative abundances of three of the four AMF species that produced spores were influenced by host identity when grown under high light (20% PAR). Furthermore, spores of one of the AMF species, Glomus geosporum , were common in soils of Luehea and Eugenia but absent in soils of Apeiba and Virola . We then conducted a reciprocal experiment to test whether AMF communities previously modified by Luehea and Apeiba differentially affected the growth of conspecific and heterospecific seedlings. Luehea seedling growth did not differ between soils containing AMF communities modified by Luehea and Apeiba . However, Apeiba seedlings were significantly larger when grown with Apeiba ‐modified AMF communities, as compared to Apeiba seedlings grown with Luehea ‐modifed AMF communities. Our experiments suggest that interactions between tropical trees and their associated AMF are species‐specific and that these interactions may shape both tree and AMF communities through plant–soil feedback.

Feature extraction for Darfur: geospatial applications in the documentation of human rights abuses - John J. Sulik; Scott Edwards (International Journal of Remote Sensing, 2010)

Improvements to Shellfish Harvest Area Closure Decision Making Using GIS, Remote Sensing, and Predictive Models - Rense Heath Kelsey; Geoffrey I. Scott; Dwayne E. Porter; Thomas C. Siewicki; Donald G. Edwards (Estuaries and Coasts, 2010)

Erratum to: Multilocus phylogeography and phylogenetics using sequence-based markers - Patrícia H. Brito; Scott V. Edwards (Genetica, 2010)

Comparative genomics based on massive parallel transcriptome sequencing reveals patterns of substitution and selection across 10 bird species - AXEL KÜNSTNER; JOCHEN B. W. WOLF; NICLAS BACKSTRÖM; OSCEOLA WHITNEY; CHRISTOPHER N. BALAKRISHNAN; LAINY DAY; SCOTT V. EDWARDS; DANIEL E. JANES; BARNEY A. SCHLINGER; RICHARD K. WILSON; ERICH D. JARVIS; WESLEY C. WARREN; et al. (Molecular Ecology, 2010)
Next‐generation sequencing technology provides an attractive means to obtain large‐scale sequence data necessary for comparative genomic analysis. To analyse the patterns of mutation rate variation and selection intensity across the avian genome, we performed brain transcriptome sequencing using Roche 454 technology of 10 different non‐model avian species. Contigs from de novo assemblies were aligned to the two available avian reference genomes, chicken and zebra finch. In total, we identified 6499 different genes across all 10 species, with ∼1000 genes found in each full run per species. We found evidence for a higher mutation rate of the Z chromosome than of autosomes (male‐biased mutation) and a negative correlation between the neutral substitution rate ( d S ) and chromosome size. Analyses of the mean d N / d S ratio (ω) of genes across chromosomes supported the Hill–Robertson effect (the effect of selection at linked loci) and point at stochastic problems with ω as an independent measure of selection. Overall, this study demonstrates the usefulness of next‐generation sequencing for obtaining genomic resources for comparative genomic analysis of non‐model organisms.

Erratum to: MHC class I genes of birds of prey: isolation, polymorphism and diversifying selection - Miguel Alcaide; Scott V. Edwards; Luis Cadahía; Juan J. Negro (Conservation Genetics, 2009)

MHC class I genes of birds of prey: isolation, polymorphism and diversifying selection - Miguel Alcaide; Scott V. Edwards; Luis Cadahía; Juan J. Negro (Conservation Genetics, 2009)

Linking stream and landscape trajectories in the southern Appalachians - Edward P. Gardiner; Andrew B. Sutherland; Rebecca J. Bixby; Mark C. Scott; Judy L. Meyer; Gene S. Helfman; E. Fred Benfield; Cathy M. Pringle; Paul V. Bolstad; David N. Wear (Environmental Monitoring and Assessment, 2009)

Looking forwards or looking backwards in avian phylogeography? A comment on Zink and Barrowclough 2008 - SCOTT EDWARDS; STAFFAN BENSCH (Molecular Ecology, 2009)

Near real‐time, autonomous detection of marine bacterioplankton on a coastal mooring in Monterey Bay, California, using rRNA‐targeted DNA probes - Christina M. Preston; Roman Marin; Scott D. Jensen; Jason Feldman; James M. Birch; Eugene I. Massion; Edward F. DeLong; Marcelino Suzuki; Kevin Wheeler; Christopher A. Scholin (Environmental Microbiology, 2009)
Summary A sandwich hybridization assay (SHA) was developed to detect 16S rRNAs indicative of phylogenetically distinct groups of marine bacterioplankton in a 96‐well plate format as well as low‐density arrays printed on a membrane support. The arrays were used in a field‐deployable instrument, the Environmental Sample Processor (ESP). The SHA employs a chaotropic buffer for both cell homogenization and hybridization, thus target sequences are captured directly from crude homogenates. Capture probes for seven of nine different bacterioplankton clades examined reacted specifically when challenged with target and non‐target 16S rRNAs derived from in vitro transcribed 16S rRNA genes cloned from natural samples. Detection limits were between 0.10–1.98 and 4.43– 12.54 fmole ml −1 homogenate for the 96‐well plate and array SHA respectively. Arrays printed with five of the bacterioplankton‐specific capture probes were deployed on the ESP in Monterey Bay, CA, twice in 2006 for a total of 25 days and also utilized in a laboratory time series study. Groups detected included marine alphaproteobacteria, SAR11, marine cyanobacteria, marine group I crenarchaea, and marine group II euryarchaea. To our knowledge this represents the first report of remote in situ DNA probe‐based detection of marine bacterioplankton.

Multilocus phylogeography and phylogenetics using sequence-based markers - Patrícia H. Brito; Scott V. Edwards (Genetica, 2009)

Avian host community structure and prevalence of West Nile virus in Chicago, Illinois - Scott R. Loss; Gabriel L. Hamer; Edward D. Walker; Marilyn O. Ruiz; Tony L. Goldberg; Uriel D. Kitron; Jeffrey D. Brawn (Oecologia, 2009)

Structure and Evolution of a New Avian MHC Class II B Gene in a Sub-Antarctic Seabird, the Thin-Billed Prion (Procellariiformes: Pachyptila belcheri) - Mónica C. Silva; Scott V. Edwards (Journal of Molecular Evolution, 2009)

Assessing the extent and diversity of riparian ecosystems in Sonora, Mexico - Michael L. Scott; Pamela L. Nagler; Edward P. Glenn; Carlos Valdes-Casillas; Joseph A. Erker; Elizabeth W. Reynolds; Patrick B. Shafroth; Euduardo Gomez-Limon; Cory L. Jones (Biodiversity and Conservation, 2009)

Characterizing microbial diversity in production water from an Alaskan mesothermic petroleum reservoir with two independent molecular methods - Vinh D. Pham; Linda L. Hnatow; Shiping Zhang; Robert D. Fallon; Scott C. Jackson; Jean‐Francois Tomb; Edward F. DeLong; Sharon J. Keeler (Environmental Microbiology, 2009)
Summary The phylogenetic diversity of Bacteria and Archaea within a biodegraded, mesothermic petroleum reservoir in the Schrader Bluff Formation of Alaska was examined by two culture‐independent methods based on fosmid and small‐subunit rRNA gene PCR clone libraries. Despite the exclusion of certain groups by each method, there was overall no significant qualitative difference in the diversity of phylotypes recovered by the two methods. The resident Bacteria belonged to at least 14 phylum‐level lineages, including the polyphyletic Firmicutes , which accounted for 36.2% of all small‐subunit rRNA gene‐containing (SSU + ) fosmid clones identified. Members of uncultured divisions were also numerous and made up 35.2% of the SSU + fosmid clones. Clones from domain Archaea accounted for about half of all SSU + fosmids, suggesting that their cell numbers were comparable to those of the Bacteria in this microbial community. In contrast to the Bacteria , however, nearly all archaeal clones recovered by both methods were related to methanogens, especially acetoclastic methanogens, while the plurality of bacterial fosmid clones was affiliated with Synergistes ‐like acetogenic Firmicutes that possibly degrade longer‐chain carboxylic acid components in the crude oil to acetate. These data suggest that acetate may be a key intermediary metabolite in this subsurface anaerobic food chain, which leads to methane production as the primary terminal electron sink.

Climatic fluctuations shape the phylogeography of a mesic direct‐developing frog from the south‐western Australian biodiversity hotspot - Danielle L. Edwards; J. Dale Roberts; J. Scott Keogh (Journal of Biogeography, 2008)
Aim To assess phylogeographic pattern throughout the range of Metacrinia nichollsi in order to develop specific biogeographical hypotheses for the wet forests of south‐western Australia. This was carried out by contrasting a direct‐developing frog species, M. nichollsi , that breeds independently of free surface water with conventional, aquatic breeders and highly specialized direct developers. Location Wet forests of the south‐western Australian biodiversity hotspot – an area of high species richness and endemism for myobatrachid frogs and many other faunal groups. Methods We compiled an extensive phylogeographic data set from field‐collected samples based on mitochondrial ND2 sequences. Phylogenetic analyses combined with estimates of divergence times were used to build a model of major biogeographical events affecting the species. Phylogeographic analyses were used to provide insights into smaller‐scale processes acting within each major lineage. Results Phylogenetic analysis recovered three major lineages, with divergence dates coincident with late Miocene–early Pliocene arid cycles. One lineage was confined to geographically isolated populations in the Stirling Ranges (Stirling Ranges Lineage, SRL). The continuous range of M. nichollsi was split into two: the Main Range Lineage (MRL) and the Southern Coastal Lineage (SCL). The SCL displays a strong drainage‐based population structure, whereas the MRL displays a strong signature of recent expansion, suggesting that these two lineages have had very different biogeographical histories. Main conclusions Late Miocene–Pliocene aridity appears to have isolated populations in the Stirling Ranges and resulted in the formation of two additional lineages on a north–south gradient that are independent of southward‐flowing drainage systems. Our results demonstrate that climatic fluctuations are likely to have generated fine‐scale phylogeographic structure within M. nichollsi and that catchment regions are important refugia during arid cycles.

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Extensive polymorphism and geographical variation at a positively selected MHC class II B gene of the lesser kestrel ( Falco naumanni ) - MIGUEL ALCAIDE; SCOTT V. EDWARDS; JUAN J. NEGRO; DAVID SERRANO; JOSÉ L. TELLA (Molecular Ecology, 2008)
Understanding the selective forces that shape genetic variation in natural populations remains a high priority in evolutionary biology. Genes at the major histocompatibility complex (MHC) have become excellent models for the investigation of adaptive variation and natural selection because of their crucial role in fighting off pathogens. Here we present one of the first data sets examining patterns of MHC variation in wild populations of a bird of prey, the lesser kestrel, Falco naumanni . We report extensive polymorphism at the second exon of a putatively functional MHC class II gene, Fana‐ DAB*1. Overall, 103 alleles were isolated from 121 individuals sampled from Spain to Kazakhstan. Bayesian inference of diversifying selection suggests that several amino acid sites may have experienced strong positive selection (ω = 4.02 per codon). The analysis also suggests a prominent role of recombination in generating and maintaining MHC diversity (ρ = 4 Nc = 0.389 per codon, θ = 0.017 per codon). Both the Fana ‐DAB*1 locus and a set of eight polymorphic microsatellite markers revealed an isolation‐by‐distance pattern across the Western Palaearctic ( r = 0.67; P = 0.01 and r = 0.50; P = 0.04, respectively). Nonetheless, geographical variation at the MHC contrasts with relatively uniform distributions in the frequencies of microsatellite alleles. In addition, we found lower fixation rates in the MHC than those predicted by genetic drift after controlling for neutral mitochondrial sequences. Our results therefore underscore the role of balancing selection as well as spatial variations in parasite‐mediated selection regimes in shaping MHC diversity when gene flow is limited.

Erratum to: Genomics and ornithology - Scott V. Edwards (Journal of Ornithology, 2008)

PERSPECTIVE: A smörgåsbord of markers for avian ecology and evolution - SCOTT V. EDWARDS (Molecular Ecology, 2008)
The polymerase chain reaction has been a boon to the study of molecular ecology and population genetics of birds. But the nagging truth is that for many bird species, the number of polymerase chain reaction (PCR) primer pairs that one can pick off the shelf and expect to amplify their target loci with ease is frustratingly small. Now, studying DNA sequence variation in natural populations of birds just got a whole lot easier. This issue of Molecular Ecology reports a large‐scale bioinformatics search for exonic sequences conserved between the chicken and zebra finch genomes and flanking polymorphic introns that has generated a staggering 242 PCR primer pairs that readily amplify their single‐copy target loci in five avian species spanning ~100 million years of avian evolution ( Backström et al . 2008 ). As proof of principle, these primers have also been used to survey the genomic landscape in over 110 kb of intronic sequence in the collared flycatcher, a model species in ecology and evolution. These resources pave the way for easy multilocus study of evolving populations and lineages of birds, and bring the goal of quickly turning nonmodel species in to ecological genomic models tantalizingly close.

Genomics and ornithology - Scott V. Edwards (Journal of Ornithology, 2007)

Hunting for Hydrothermal Vents Along the Galápagos Spreading Center - Raychel Haymon; Edward Baker; Joseph Resing; Scott White; Ken McDonald (Oceanography, 2007)

Characterization, Polymorphism, and Evolution of MHC Class II B Genes in Birds of Prey - Miguel Alcaide; Scott V. Edwards; Juan J. Negro (Journal of Molecular Evolution, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Improved drought tolerance of transgenic Zea mays plants that express the glutamate dehydrogenase gene (gdhA) of E. coli - David A. Lightfoot; Rajsree Mungur; Rafiqa Ameziane; Scott Nolte; Lynn Long; Karen Bernhard; Andrew Colter; Karen Jones; M. J. Iqbal; Edward Varsa; Brian Young (Euphytica, 2007)

Impact of Plio‐Pleistocene arid cycling on the population history of a southwestern Australian frog - DANIELLE L. EDWARDS; J. DALE ROBERTS; J. SCOTT KEOGH (Molecular Ecology, 2007)
Southwestern Australia is regarded as a global biodiversity hotspot. The region contains a high number of endemic species, ranging from Gondwanan relicts to much more recently evolved plant and animal species. Myobatrachid frogs are diverse in southwestern Australia, and while we know they have speciated in situ in the southwest, we know little about the temporal and geographical patterning of speciation events. Crinia georgiana is an ideal subject to test hypotheses concerning the effect of climatic history on southwestern Australian anurans, as it is an old lineage with a broad distribution covering the entire region. We compiled an extensive phylogeographical data set based on 1085 bp of the mitochondrial gene ND2 for 68 individuals from 18 sites across the species’ range. Two major genetic clades were identified which were largely confined to the high rainfall and southeast coastal biogeographical zones, respectively. The clades appear to have diverged around the Plio‐Pleistocene border (1.26–1.72 million years ago), concordant with increasing intensity and frequency of arid climate cycles. Subsequent phylogeographical structure appears to have developed primarily during the Pleistocene climatic fluctuations that also have been integral in generating species diversity in the endemic southwestern Australian flora. Phylogeographical analyses identified several dispersal routes, possible refugial areas within the range of the species and also regions of secondary contact. Dispersal routes identified may now be closed to the species because of habitat destruction and salinity problems in inland regions, posing concerns about the evolutionary potential of the species in light of predicted climate change.

A GIS Tool to Estimate West Nile Virus Risk Based on a Degree-Day Model - Li Zou; Scott N. Miller; Edward T. Schmidtmann (Environmental Monitoring and Assessment, 2007)

Measuring RNA:DNA ratios in individual Acartia tonsa (Copepoda) - Christa L. Speekmann; B. Scott Nunez; Edward J. Buskey (Marine Biology, 2007)

Evolutionary genetics of Carpodacus mexicanus, a recently colonized host of a bacterial pathogen, Mycoplasma gallisepticum - Christopher M. Hess; Zhenshan Wang; Scott V. Edwards (Genetica, 2007)

A reassessment of the mating system characteristics of the army ant Eciton burchellii - Daniel J. C. Kronauer; Stefanie M. Berghoff; Scott Powell; A. Jay Denny; Keith J. Edwards; Nigel R. Franks; Jacobus J. Boomsma (The Science of Nature, 2006)

Relationship of intertidal surface sediment chlorophyll concentration to hyperspectral reflectance and chlorophyll fluorescence - Jacco C. Kromkamp; Edward P. Morris; Rodney M. Forster; Claire Honeywill; Scott Hagerthey; David M. Paterson (Estuaries and Coasts, 2006)

A cDNA macroarray approach to parasite‐induced gene expression changes in a songbird host: genetic response of house finches to experimental infection by Mycoplasma gallisepticum - ZHENSHAN WANG; KRISTY FARMER; GEOFFREY E. HILL; SCOTT V. EDWARDS (Molecular Ecology, 2006)
In 1994, the bacterial parasite Mycoplasma gallisepticum expanded its host range and swept through populations of a novel host — eastern US populations of the house finch ( Carpodacus mexicanus ). This epizootic caused a dramatic decline in finch population numbers, has been shown to have caused strong selection on house finch morphology, and presumably caused evolutionary change at the molecular level as finches evolved enhanced resistance. As a first step toward identifying finch genes that respond to infection by Mycoplasma and which may have experienced natural selection by this parasite, we used suppression subtractive hybridization (SSH) and cDNA macroarray approaches to identify differentially expressed genes regulated by the Mycoplasma parasite. Two subtractive cDNA libraries consisting of 16 512 clones were developed from spleen using an experimentally uninfected bird as the ‘tester’ and an infected bird as ‘driver’, and vice versa. Two hundred and twenty cDNA clones corresponding 34 genes with known vertebrate homologues and a large number of novel transcripts were found to be qualitatively up‐ or down‐regulated genes by high‐density filter hybridization. These gene expression changes were further confirmed by a high throughout reverse Northern blot approach and in specific cases by targeted Northern analysis. blast searches show that heat shock protein (HSP) 90, MHC II‐associated invariant chain (CD74), T‐cell immunoglobulin mucin 1 (TIM1), as well as numerous novel expressed genes not found in the databases were up‐ or down‐regulated by the host in response to this parasite. Our results and macroarray resources provide a foundation for molecular co‐evolutionary studies of the Mycoplasma parasite and its recently colonized avian host.

Mental maze solving: directional fMRI tuning and population coding in the superior parietal lobule - Pavlos Gourtzelidis; Charidimos Tzagarakis; Scott M. Lewis; David A. Crowe; Edward Auerbach; Trenton A. Jerde; Kâmil Uğurbil; Apostolos P. Georgopoulos (Experimental Brain Research, 2005)

Milk thistle and indinavir: a randomized controlled pharmacokinetics study and meta-analysis - Edward Mills; Kumanan Wilson; Mike Clarke; Brian Foster; Scott Walker; Beth Rachlis; Nick DeGroot; Victor M. Montori; Wayne Gold; Elizabeth Phillips; Stephen Myers; Keith Gallicano (European Journal of Clinical Pharmacology, 2005)

Diversity of arbuscular mycorrhizal fungi across a fragmented forest in Panama: insular spore communities differ from mainland communities - Scott A. Mangan; Ahn-Heum Eom; Gregory H. Adler; Joseph B. Yavitt; Edward A. Herre (Oecologia, 2004)

Exceptionally high levels of multiple mating in an army ant - A.Jay Denny; NigelR. Franks; Scott Powell; KeithJ. Edwards (The Science of Nature, 2004)

Electrical stimulation driving functional improvements and cortical changes in subjects with stroke - Teresa J. Kimberley; Scott M. Lewis; Edward J. Auerbach; Lisa L. Dorsey; Jeanne M. Lojovich; James R. Carey (Experimental Brain Research, 2004)

fMRI analysis of ankle movement tracking training in subject with stroke - Edward J. Auerbach; Kamil Ugurbil; James R. Carey; Kathleen M. Anderson; Teresa J. Kimberley; Scott M. Lewis (Experimental Brain Research, 2004)

Adolescent-onset nicotine self-administration modeled in female rats - Edward D. Levin; Amir H. Rezvani; Daniel Montoya; Jed E. Rose; H. Scott Swartzwelder (Psychopharmacology, 2003)

Targeted suppression of the ferroxidase and iron trafficking activities of the multicopper oxidase Fet3p from Saccharomyces cerevisiae - Tzu-Pin Wang; Liliana Quintanar; Scott Severance; Edward I. Solomon; Daniel J. Kosman (JBIC Journal of Biological Inorganic Chemistry, 2003)

Class I molecules with similar peptide-binding specificities are the result of both common ancestry and convergent evolution - Alessandro Sette; John Sidney; Brian D. Livingston; John L. Dzuris; Claire Crimi; Christopher M. Walker; Scott Southwood; Edward J. Collins; Austin L. Hughes (Immunogenetics, 2003)

Effect of sucrose concentration on elongation of shoots from flax anther culture - Yurong Chen; Shirley Lin; Scott Duguid; Paul Dribnenki; Edward Kenaschuk (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)

Summary findings of the fourth international radiocarbon intercomparison (FIRI)(1998–2001) - Elisabetta Boaretto; Charlotte Bryant; Israel Carmi; Gordon Cook; Steinar Gulliksen; Doug Harkness; Jan Heinemeier; John McClure; Edward McGee; Philip Naysmith; Goran Possnert; Marian Scott; et al. (Journal of Quaternary Science, 2002)
Interlaboratory comparisons have been widely used in applied radiocarbon science. These are an important part of ongoing quality assurance (QA) programmes, which are vital to the appropriate interpretation of the evidence provided by the 14 C record in Quaternary applications (including climate change and environmental reconstruction). International comparisons of laboratory performance are an essential component of the quality assurance process in radiocarbon dating. If the user community is to have confidence in radiocarbon results, it needs to be assured that laboratories world wide are producing measurements that are reliable and in accordance with ‘good practice’. The findings from the most recent (completed in 2001) and extensive (more than 90 participating laboratories) radiocarbon intercomparison (FIRI) are reported here. This study was designed (i) to assess comparability, or otherwise, of the results from different laboratories and (ii) to quantify the extent and possible causes of any interlaboratory variation. The results demonstrate that there are no significant differences amongst the main measurement techniques (gas proportional counting, liquid scintillation counting and accelerator mass spectrometry (AMS)) but there is evidence of small laboratory offsets relative to known age samples for some laboratories. There is also evidence in some cases of underestimation of measurement precision. Approximately 10% of all results were classified as extreme (outliers) and these results were generated by 14% of the laboratories. Overall, the evidence supports the fact that radiocarbon laboratories are generally accurate and precise but that, notwithstanding internal QA procedures, some problems still occur, which can best be detected by participation in independent intercomparisons such as FIRI, where the results allow individual laboratories to assess their performance and to take remedial measures where necessary. The results from FIRI are significant in that they show a broad measure of agreement between measurements made in different laboratories on a wide range of materials and they also demonstrate no statistically significant difference between measurements made by radiometric or AMS techniques. Copyright © 2002 John Wiley & Sons, Ltd.

Regulation of cell morphology and cytochrome P450 expression in human hepatocytes by extracellular matrix and cell-cell interactions - James Coon; Geraldine Hamilton; Summer Jolley; Darryl Gilbert; Scott Barros; Edward LeCluyse (Cell and Tissue Research, 2001)

Erratum to: Dynamics and Phylogenetic Implications of MtDNA Control Region Sequences in New World Jays (Aves: Corvidae) - Matthew A. Saunders; Scott V. Edwards (Journal of Molecular Evolution, 2001)

Ontogeny of Alarm Pheromone Secretion in Pea Aphid, Acyrthosiphon pisum - Edward B. Mondor; D. Scott Baird; K. N. Slessor; B. D. Roitberg (Journal of Chemical Ecology, 2000)

Dynamics and Phylogenetic Implications of MtDNA Control Region Sequences in New World Jays (Aves: Corvidae) - Matthew A. Saunders; Scott V. Edwards (Journal of Molecular Evolution, 2000)

Liposome associated interferon-alpha-2b functions as an anti-fibrogenic factor in dermal wounds in the guinea pig - Aziz Ghahary; Edward E. Tredget; Qiong Shen; Ruhangiz T. Kilani; Paul G. Scott; Masaki Takeuchi (Molecular and Cellular Biochemistry, 2000)

UTILITY OF GENDER DETERMINATION IN CELL LINE IDENTITY - A. SCOTT DURKIN; EDWARD CEDRONE; GREGORY SYKES; DEBRA BOLES; YVONNE A. REID (In Vitro Cellular & Developmental Biology - Animal, 2000)

Regulating exercise intensity using ratings of perceived exertion during arm and leg ergometry - Jie Kang; Edward C. Chaloupka; M. Alysia Mastrangelo; M. Scott Donnelly; William P. Martz; Robert J. Robertson (European Journal of Applied Physiology, 1998)

Expression and localization of insulin-like growth factor-1 in normal and post-burn hypertrophic scar tissue in human - Aziz Ghahary; You J. Shen; Rijian Wang; Paul G. Scott; Edward E. Tredget (Molecular and Cellular Biochemistry, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Atmospheric Effects of the Emerging Mainland Chinese Transportation System at and Beyond the Regional Scale - SCOTT ELLIOTT; MEI SHEN; DONALD R. BLAKE; RONG LU; ARMISTEAD G. RUSSELL; C. Y. J. KAO; GERALD E. STREIT; XUE PENG ZHAO; EDWARD IAIN McCREARY; F. SHERWOOD ROWLAND; MICHAEL J. BROWN; RICHARD P. TURCO (Journal of Atmospheric Chemistry, 1997)

The identification, cloning, and sequence analysis of the coat protein coding region of a birch isolate (I2) of cherry leaf roll nepovirus - N. W. Scott; J. I. Cooper; M. L. Edwards (Archives of Virology, 1993)